Transfer film, laminate manufacturing method, and circuit wiring manufacturing method

JP7635244B2Active Publication Date: 2025-02-25FUJIFILM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022544472
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-25
Filing Date
2021-08-17
Publication Date
2025-02-25
Estimated Expiration
2041-08-17

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、転写フィルムを被転写体に貼り合わせた際に、シワが発生しにくい転写フィルムの提供できる。また、本発明によれば、転写フィルムを用いる積層体の製造方法及び回路配線の製造方法の提供もできる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635244000031
    Figure 0007635244000031
  • Figure 0007635244000001
    Figure 0007635244000001
  • Figure 0007635244000002
    Figure 0007635244000002
Patent Text Reader

Abstract

The present invention provides a transfer film, a laminate manufacturing method, and a circuit wiring manufacturing method in which wrinkles are less likely to occur, when the transfer film is attached to a transfer target. The transfer film of the present invention is a long transfer film having a temporary support and a photosensitive composition layer arranged on the temporary support, wherein the ratio of a storage elastic modulus Ea1 at 100°C in the lateral direction of the temporary support to a storage elastic modulus Ea2 at 100°C in the longitudinal direction of the temporary support is 1.40 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a transfer film, a laminate, and a method for producing circuit wiring. [Background technology]

[0002] Because the number of steps required to obtain a desired pattern is small, a method is widely used in which a photosensitive composition layer is placed on a transfer object such as a substrate using a transfer film, and the photosensitive composition layer is exposed to light through a mask and then developed.

[0003] For example, Patent Document 1 discloses a photosensitive film (transfer film) for producing a color filter. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-324210 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, there has been a demand for further improvement in the performance of transfer films. Specifically, there has been a demand for transfer films that are less likely to wrinkle when the surface of the transfer film opposite the temporary support is brought into contact with and bonded to a transfer target.

[0006] The present inventors have studied the characteristics of the transfer film described in Patent Document 1 and the like and have found that wrinkles occur during lamination and that further improvements are necessary.

[0007] Therefore, an object of the present invention is to provide a transfer film that is less likely to wrinkle when attached to a receiving body. Another object of the present invention is to provide a method for producing a laminate and a method for producing circuit wiring using a transfer film. [Means for solving the problem]

[0008] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by the following configuration.

[0009] [1] A long-sized transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support, the temporary support having a storage modulus E at 100° C. in the longitudinal direction thereof a2 Storage modulus E at 100 ° C in the short direction of the temporary support a1 A transfer film, wherein the ratio is 1.40 or less. [2] The transfer film according to [1], wherein X calculated by formula (1) is 7.00% or less. X={〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 )}×100 Equation (1) E a1 : Storage modulus of the temporary support in the short direction at 100°C (GPa) E a2 : Storage modulus of the temporary support in the longitudinal direction at 100°C (GPa) E b1 : Storage modulus of the temporary support in the short direction at 80°C (GPa) E b2 : Storage modulus of the temporary support in the longitudinal direction at 80°C (GPa) [3] Storage modulus E of the temporary support in the short direction at 100°C a1 and the storage modulus E of the temporary support in the longitudinal direction at 100 ° C. a2 The transfer film according to [1] or [2], wherein the geometric mean of the surface tension is 1.00 GPa or more. [4] The transfer film according to any one of [1] to [3], wherein the thickness of the temporary support is 40.0 μm or less. [5] The transfer film according to any one of [1] to [4], wherein the photosensitive composition layer has a thickness of 20.0 μm or less. [6] The transfer film according to any one of [1] to [5], wherein the photosensitive composition layer contains a binder polymer, a polymerizable compound, and a polymerization initiator. [7] The transfer film according to any one of [1] to [6], further comprising a refractive index adjusting layer disposed on the photosensitive composition layer. [8] The transfer film according to any one of [1] to [7], wherein the photosensitive composition layer is used for forming an electrode protective film for a touch panel. [9] a lamination step of laminating a surface of the transfer film according to any one of [1] to [8] opposite to the temporary support to a transferee to obtain a transferee with a photosensitive composition layer having the transferee, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A developing step of developing the exposed photosensitive composition layer to form a pattern, The method for producing a laminate further comprises a peeling step of peeling the temporary support from the transfer-receiving body with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.

[10] a lamination step of laminating a surface of the transfer film according to any one of [1] to [8] opposite to the temporary support to a transfer-receiving body including a conductive layer to obtain a transfer-receiving body with a photosensitive composition layer having the transfer-receiving body, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; a developing step of developing the exposed photosensitive composition layer to form a pattern; an etching step for etching the conductive layer in areas where no pattern is disposed; The method for producing circuit wiring further comprises a peeling step of peeling the temporary support from the transfer recipient with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.

[11] The method for producing a laminate according to [9], wherein the transferred object is a substrate having a step. Effect of the Invention

[0010] According to the present invention, it is possible to provide a transfer film that is less likely to cause wrinkles when attached to a transfer target. In addition, according to the present invention, it is also possible to provide a method for manufacturing a laminate using the transfer film and a method for manufacturing circuit wiring. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a substrate having a step. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the present specification, in the numerical ranges described stepwise, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described stepwise. In the numerical ranges described in the present specification, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0013] In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0014] In this specification, the term "transparent" means that the average transmittance of visible light with a wavelength of 400 to 700 nm is 80% or more, and preferably 90% or more. In this specification, the average transmittance of visible light is a value measured using a spectrophotometer, and can be measured using, for example, a spectrophotometer U-3310 manufactured by Hitachi, Ltd.

[0015] In this specification, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) are values ​​converted using polystyrene as a standard substance measured by a gel permeation chromatography (GPC) analyzer using three TSK gel Super HZM-N (manufactured by Tosoh Corporation) columns connected in series, THF (tetrahydrofuran) as an eluent, a differential refractometer as a detector, and polystyrene as a standard substance. In this specification, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is the weight average molecular weight.

[0016] In this specification, unless otherwise specified, the refractive index is a value measured by an ellipsometer using light with a wavelength of 550 nm.

[0017] In this specification, "(meth)acrylic" is a concept that includes both acrylic and methacrylic, "(meth)acrylate" is a concept that includes both acrylate and methacrylate, and "(meth)acryloxy group" is a concept that includes both acryloxy group and methacryloxy group. In addition, in this specification, the term "organic group" refers to a group containing at least one carbon atom.

[0018] In this specification, when "may have a substituent", the type of the substituent, the position of the substituent, and the number of the substituent are not particularly limited. The number of the substituents may be, for example, one, two, three, or more. Examples of the substituents include monovalent nonmetallic atomic groups other than hydrogen atoms, and can be selected from the following substituents T. (substituent T) Examples of the substituent T include halogen atoms such as fluorine atom, chlorine atom, bromine atom, and iodine atom; alkoxy groups such as methoxy group, ethoxy group, and tert-butoxy group; aryloxy groups such as phenoxy group and p-tolyloxy group; alkoxycarbonyl groups such as methoxycarbonyl group, butoxycarbonyl group, and phenoxycarbonyl group; acyloxy groups such as acetoxy group, propionyloxy group, and benzoyloxy group; acyl groups such as acetyl group, benzoyl group, isobutyryl group, acryloyl group, methacryloyl group, and methoxalyl group. groups; alkylsulfanyl groups such as methylsulfanyl group and tert-butylsulfanyl group; arylsulfanyl groups such as phenylsulfanyl group and p-tolylsulfanyl group; alkyl groups; cycloalkyl groups; aryl groups; heteroaryl groups; hydroxyl groups; carboxy groups; formyl groups; sulfo groups; cyano groups; nitro groups; ether groups; alkylaminocarbonyl groups; arylaminocarbonyl groups; sulfonamide groups; silyl groups; amino groups; monoalkylamino groups; dialkylamino groups; arylamino groups; and combinations thereof.

[0019] [Transfer film] The transfer film is a long-sized film having a temporary support and a photosensitive composition layer disposed on the temporary support. The term "long" refers to a shape in which the length of the transfer film in one direction is longer than the length in another direction perpendicular to the one direction. In other words, the transfer film has a longitudinal direction along the flow direction and a transverse direction along the width direction.

[0020] A characteristic feature of the transfer film of the present invention is that the transfer film has a temporary support having a predetermined storage modulus, as will be described later. The inventors of the present invention have studied conventional transfer films and found that when the surface of the transfer film opposite to the temporary support is brought into contact with an object to be transferred and laminated, wrinkles tend to occur. In contrast, the inventors of the present invention have found that wrinkles are less likely to occur when a transfer film having a temporary support with a predetermined storage modulus is used. Although the mechanism of wrinkle suppression is unclear, it is speculated that the use of a temporary support with small anisotropy during lamination allows for more uniform lamination, resulting in less wrinkles. Hereinafter, in this specification, the fact that wrinkles are less likely to occur is also referred to as the effect of the present invention being more excellent. Each component of the transfer film will be described in detail below.

[0021] <Temporary support> The transfer film has a temporary support. Storage modulus E at 100°C in the longitudinal direction of the temporary support a2 Storage modulus E at 100 ° C in the short direction of the temporary support a1 The ratio (E a1 / E a2 ) is 1.40 or less, and from the viewpoint of better effects of the present invention, it is preferably 1.35 or less, more preferably 1.30 or less, even more preferably 1.25 or less, particularly preferably 1.20 or less, and most preferably 1.10 or less. There is no particular lower limit, and it is preferably 0.10 or more, more preferably 0.50 or more, even more preferably 0.80 or more, and particularly preferably 1.00 or more. The temporary support is a member that supports the photosensitive composition layer and the like, which will be described later, and is ultimately removed by a peeling treatment.

[0022] In the temporary support, X calculated by formula (1) is preferably 8.00% or less, more preferably 7.00% or less, further preferably 6.80% or less, and particularly preferably 6.70% or less. X={〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 )}×100 Equation (1) E a1 : Storage modulus of the temporary support in the short direction at 100°C (GPa) E a2 : Storage modulus of the temporary support in the longitudinal direction at 100°C (GPa) E b1 : Storage modulus of the temporary support in the short direction at 80°C (GPa) E b2 : Storage modulus of the temporary support in the longitudinal direction at 80°C (GPa)

[0023] Storage modulus E at 100°C in the short direction of the temporary support a1 is preferably 1.00 to 5.00 GPa, more preferably 2.00 to 4.00 GPa, further preferably 2.00 to 2.95 GPa, particularly preferably 2.50 to 2.90 GPa, and most preferably 2.50 to 2.70 GPa. Storage modulus E at 100°C in the longitudinal direction of the temporary support a2 is preferably 1.00 to 5.00 GPa, more preferably 2.00 to 4.00 GPa, further preferably 2.15 to 3.00 GPa, particularly preferably 2.20 to 2.80 GPa, and most preferably 2.30 to 2.60 GPa. Storage modulus E at 80°C in the short direction of the temporary support b1 is preferably 1.00 to 5.00 GPa, more preferably 3.00 to 5.00 GPa, further preferably 3.50 to 4.65 GPa, particularly preferably 3.50 to 4.50 GPa, and most preferably 4.00 to 4.40 GPa. Storage modulus E at 80°C in the longitudinal direction of the temporary support b2 is preferably 1.00 to 5.00 GPa, more preferably 2.00 to 4.00 GPa, further preferably 3.18 to 4.00 GPa, particularly preferably 3.25 to 4.00 GPa, and most preferably 3.30 to 3.80 GPa.

[0024] The storage modulus can be measured, for example, by using a dynamic viscoelasticity measuring device (Vibron: DVA-225 (manufactured by IT Measurement and Control Co., Ltd.)).

[0025] Storage modulus E of the temporary support in the short direction at 100°C a1 and the storage modulus E of the temporary support in the longitudinal direction at 100 ° C. a2 The geometric mean of the tensile strength is preferably 1.00 GPa or more, more preferably 2.00 GPa or more, and even more preferably 2.40 GPa or more. There is no particular upper limit, but it is preferably 5.00 GPa or less, and more preferably 3.00 GPa or less. The geometric mean is the nth root of the product of n numbers. For example, E a1 and E a2 The square root of the product of (geometric mean = √(E a1 ×E a2 )).

[0026] The above characteristics of the temporary support ((E a1 / E a2 The means for achieving the above properties are not particularly limited, and known methods can be used. For example, when a biaxially stretched resin film (e.g., a biaxially stretched polyethylene terephthalate film) is used as the temporary support, the above properties can be achieved by adjusting the stretching ratios in the longitudinal and transverse directions.

[0027] The temporary support is preferably a film, and more preferably a resin film. As the temporary support, a film that has flexibility and does not significantly deform, shrink, or elongate under pressure or under pressure and heat can be used. Examples of the film include polyethylene terephthalate film (PET) (eg, biaxially oriented polyethylene terephthalate film), cellulose triacetate film, polystyrene film, polyimide film, and polycarbonate film. Among them, the temporary support is preferably a biaxially stretched polyethylene terephthalate film. It is also preferable that the film used as the temporary support is free from deformation such as wrinkles and scratches.

[0028] The temporary support preferably has high transparency so that pattern exposure can be performed through the temporary support, and the transmittance of light with a wavelength of 365 nm is preferably 60% or more, more preferably 70% or more. From the viewpoint of pattern formability during pattern exposure through the temporary support and transparency of the temporary support, the haze of the temporary support is preferably small. Specifically, the haze value of the temporary support is preferably 2% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. There is no particular lower limit, and 0% or more is preferable. From the viewpoints of pattern formability during pattern exposure through the temporary support and transparency of the temporary support, it is preferable that the number of fine particles, foreign matter, and defects contained in the temporary support is small. The number of fine particles, foreign matter, and defects having a diameter of 1 μm or more is 50 / 10 mm. 2 Less than 10 pieces / 10mm is preferable. 2 Less than 3 pieces / 10mm is more preferable. 2 Less than 0 / 10mm is more preferable. 2 is particularly preferred.

[0029] The thickness of the temporary support is not particularly limited, but is often 200.0 μm or less, and from the viewpoint of better effect of the present invention, it is preferably 100.0 μm or less, more preferably 40.0 μm or less, even more preferably 30.0 μm or less, particularly preferably 25.0 μm or less, and most preferably 20.0 μm or less. There is no particular lower limit, but it is preferably 1.0 μm or more, and more preferably 10.0 μm or more. The thickness of the temporary support can be calculated as the average value of any five points measured by cross-sectional observation using a scanning electron microscope (SEM).

[0030] A layer containing fine particles (lubricant layer) may be provided on the surface of the temporary support in order to provide handling properties. The lubricant layer may be provided on one side or both sides of the temporary support. The diameter of the particles contained in the lubricant layer is preferably 0.05 to 0.8 μm. The thickness of the lubricant layer is preferably 0.05 to 1.0 μm.

[0031] Examples of the temporary support include a biaxially oriented polyethylene terephthalate film having a thickness of 25.0 μm, a biaxially oriented polyethylene terephthalate film having a thickness of 16.0 μm, and a biaxially oriented polyethylene terephthalate film having a thickness of 12.0 μm.

[0032] Preferred forms of the temporary support can be found, for example, in paragraphs

[0017] to

[0018] of JP 2014-085643 A, paragraphs

[0019] to

[0026] of JP 2016-027363 A, paragraphs

[0041] to

[0057] of WO 2012 / 081680 A1, and paragraphs

[0029] to

[0040] of WO 2018 / 179370 A1, the contents of which are incorporated herein by reference.

[0033] <Photosensitive composition layer> The transfer film has a photosensitive composition layer disposed on a temporary support. The photosensitive composition layer preferably contains a binder polymer, a polymerizable compound, and a polymerization initiator, which will be described later. After the photosensitive composition layer is transferred onto the transfer-receiving material, exposure and development are carried out, whereby a pattern can be formed on the transfer-receiving material. The photosensitive composition layer may be a positive-type photosensitive composition layer or a negative-type photosensitive composition layer. The positive-type photosensitive composition layer is a photosensitive composition layer in which the solubility in a developer of the exposed portion is improved by exposure, whereas the negative-type photosensitive composition layer is a photosensitive composition layer in which the solubility in a developer of the exposed portion is reduced by exposure. Among them, it is preferable to use a negative photosensitive composition layer. When the photosensitive composition layer is a negative photosensitive composition layer, the formed pattern corresponds to a protective film.

[0034] From the viewpoint of coatability, the thickness of the photosensitive composition layer is preferably 20.0 μm or less, more preferably 15.0 μm or less, and even more preferably 10.0 μm or less. The lower limit is not particularly limited, and is preferably 0.05 μm or more, more preferably 3.0 μm or more, even more preferably 4.0 μm or more, and particularly preferably 5.0 μm or more. The thickness of the photosensitive composition layer is calculated as the average value of measurements at any five points by cross-sectional observation using a scanning electron microscope (SEM).

[0035] The refractive index of the photosensitive composition layer is preferably from 1.47 to 1.56, and more preferably from 1.49 to 1.54.

[0036] The photosensitive composition layer is preferably achromatic. * The value is preferably −1.0 to 1.0, and the b * The value is preferably in the range of -1.0 to 1.0. The hue of the photosensitive composition layer can be measured using a color difference meter (CR-221, manufactured by Minolta Co., Ltd.).

[0037] The NCO value of the photosensitive composition layer is preferably greater than 0.50 mmol / g, more preferably 0.55 mmol / g or more, and even more preferably 0.60 mmol / g or more. The upper limit of the NCO value of the photosensitive composition layer is preferably 1.0 mmol / g or less, more preferably less than 0.80 mmol / g, and further preferably 0.70 mmol / g or less. The NCO value of the photosensitive composition layer means the number of moles of isocyanate groups contained per gram of the photosensitive composition layer, and is a value calculated from the structural formula of the blocked isocyanate compound.

[0038] Each material constituting the photosensitive composition layer will now be described.

[0039] [Binder polymer] The photosensitive composition layer may contain a binder polymer. Examples of the binder polymer include (meth)acrylic resin, styrene resin, epoxy resin, amide resin, amide epoxy resin, alkyd resin, phenol resin, ester resin, urethane resin, epoxy acrylate resin obtained by reacting an epoxy resin with (meth)acrylic acid, and acid-modified epoxy acrylate resin obtained by reacting an epoxy acrylate resin with an acid anhydride.

[0040] One preferred embodiment of the binder polymer is a (meth)acrylic resin, which has excellent alkali developability and film formability. In this specification, the (meth)acrylic resin means a resin having a structural unit derived from a (meth)acrylic compound. The content of the structural unit derived from a (meth)acrylic compound is preferably 50% by mass or more, more preferably 70% by mass or more, based on the total structural units of the (meth)acrylic resin. The (meth)acrylic resin may be composed only of structural units derived from (meth)acrylic compounds, or may have structural units derived from polymerizable monomers other than (meth)acrylic compounds. That is, the upper limit of the content of structural units derived from (meth)acrylic compounds is preferably 100% by mass or less based on the total structural units of the (meth)acrylic resin.

[0041] Examples of the (meth)acrylic compound include (meth)acrylic acid, (meth)acrylic acid esters, (meth)acrylamide, and (meth)acrylonitrile. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl ester, (meth)acrylic acid tetrahydrofurfuryl ester, (meth)acrylic acid dimethylaminoethyl ester, (meth)acrylic acid diethylaminoethyl ester, (meth)acrylic acid glycidyl ester, (meth)acrylic acid benzyl ester, 2,2,2-trifluoroethyl (meth)acrylate, and 2,2,3,3-tetrafluoropropyl (meth)acrylate, and (meth)acrylic acid alkyl ester is preferred. Examples of (meth)acrylamides include acrylamides such as diacetoneacrylamide.

[0042] Examples of the (meth)acrylic acid alkyl ester include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 12 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. As the (meth)acrylic acid ester, a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 4 carbon atoms is preferred, and methyl (meth)acrylate or ethyl (meth)acrylate is more preferred.

[0043] The (meth)acrylic resin may have a structural unit other than the structural unit derived from the (meth)acrylic compound. The polymerizable monomer that forms the above-mentioned structural unit is not particularly limited as long as it is a compound other than a (meth)acrylic compound that is copolymerizable with a (meth)acrylic compound, and examples thereof include styrene compounds that may have a substituent at the α-position or aromatic ring, such as styrene, vinyl toluene, and α-methyl styrene, vinyl alcohol esters such as acrylonitrile and vinyl-n-butyl ether, maleic acid, maleic anhydride, maleic acid monoesters such as monomethyl maleate, monoethyl maleate, and monoisopropyl maleate, fumaric acid, cinnamic acid, α-cyanocinnamic acid, itaconic acid, and crotonic acid. These polymerizable monomers may be used alone or in combination of two or more.

[0044] In order to improve the alkali developability, the (meth)acrylic resin preferably has a structural unit having an acid group. Examples of the acid group include a carboxy group, a sulfo group, a phosphoric acid group, and a phosphonic acid group. Among these, the (meth)acrylic resin more preferably has a structural unit having a carboxy group, and even more preferably has a structural unit derived from the above-mentioned (meth)acrylic acid.

[0045] The content of the structural unit having an acid group in the (meth)acrylic resin (preferably a structural unit derived from (meth)acrylic acid) is preferably 10% by mass or more based on the total mass of the (meth)acrylic resin in terms of excellent developability. The upper limit is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, in terms of excellent alkali resistance.

[0046] Moreover, the (meth)acrylic resin more preferably has a structural unit derived from the above-mentioned (meth)acrylic acid alkyl ester. The content of structural units derived from an alkyl (meth)acrylate in the (meth)acrylic resin is preferably 50 to 90 mass %, more preferably 60 to 90 mass %, and even more preferably 65 to 90 mass %, based on all structural units of the (meth)acrylic resin.

[0047] As the (meth)acrylic resin, a resin having both a structural unit derived from (meth)acrylic acid and a structural unit derived from a (meth)acrylic acid alkyl ester is preferred, and a resin composed only of a structural unit derived from (meth)acrylic acid and a structural unit derived from a (meth)acrylic acid alkyl ester is more preferred. Furthermore, as the (meth)acrylic resin, an acrylic resin having a structural unit derived from methacrylic acid, a structural unit derived from methyl methacrylate, and a structural unit derived from ethyl acrylate is also preferred.

[0048] In addition, in order to obtain a more excellent effect of the present invention, the (meth)acrylic resin preferably has at least one selected from the group consisting of a structural unit derived from methacrylic acid and a structural unit derived from an alkyl methacrylate ester, and more preferably has both a structural unit derived from methacrylic acid and a structural unit derived from an alkyl methacrylate ester. The total content of the structural units derived from methacrylic acid and the structural units derived from methacrylic acid alkyl ester in the (meth)acrylic resin is preferably 40% by mass or more, more preferably 60% by mass or more, based on the total structural units of the (meth)acrylic resin, in order to obtain a more excellent effect of the present invention. The upper limit is not particularly limited, and may be 100% by mass or less, and is preferably 80% by mass or less.

[0049] In addition, in terms of obtaining better effects of the present invention, it is also preferable that the (meth)acrylic resin has at least one selected from the group consisting of structural units derived from methacrylic acid and structural units derived from an alkyl methacrylate ester, and at least one selected from the group consisting of structural units derived from acrylic acid and structural units derived from an alkyl acrylate ester. In order to obtain a more excellent effect of the present invention, the total content of the structural units derived from methacrylic acid and the structural units derived from an alkyl methacrylate ester is preferably 60 / 40 to 80 / 20 in mass ratio relative to the total content of the structural units derived from acrylic acid and the structural units derived from an alkyl acrylate ester.

[0050] The (meth)acrylic resin preferably has an ester group at the end, in view of excellent developability of the photosensitive composition layer after transfer. The terminal portion of the (meth)acrylic resin is composed of a portion derived from the polymerization initiator used in the synthesis. The (meth)acrylic resin having an ester group at the terminal can be synthesized by using a polymerization initiator that generates a radical having an ester group.

[0051] Another preferred embodiment of the binder polymer is an acrylic-soluble resin. In this disclosure, "alkali-soluble" means that the solubility in 100 g of a 1% by mass aqueous solution of sodium carbonate at 22°C is 0.1 g or more. From the viewpoint of developability, the binder polymer is preferably a binder polymer having an acid value of 60 mgKOH / g or more. In addition, the binder polymer is more preferably a resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing resin), and even more preferably a (meth)acrylic resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing (meth)acrylic resin), from the viewpoint of being easily thermally crosslinked with the crosslinking component by heating to form a strong film. When the binder polymer is a resin having a carboxy group, the three-dimensional crosslinking density can be increased by, for example, adding a thermally crosslinkable compound such as a blocked isocyanate compound to thermally crosslink the resin. In addition, when the carboxy group of the resin having a carboxy group is dehydrated and hydrophobized, the humidity and heat resistance can be improved.

[0052] The carboxyl group-containing (meth)acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited as long as it satisfies the above-mentioned acid value condition, and can be appropriately selected from known (meth)acrylic resins. For example, of the polymers described in paragraph

[0025] of JP-A-2011-095716, a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more can be preferably used, and of the polymers described in paragraphs

[0033] to

[0052] of JP-A-2010-237589, a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more can be preferably used.

[0053] Another preferred embodiment of the binder polymer is a styrene-acrylic copolymer. In the present disclosure, the styrene-acrylic copolymer refers to a resin having a structural unit derived from a styrene compound and a structural unit derived from a (meth)acrylic compound, and the total content of the structural unit derived from the styrene compound and the structural unit derived from the (meth)acrylic compound is preferably 30% by mass or more, more preferably 50% by mass or more, based on the total structural units of the copolymer. The lower limit is not particularly limited, but is preferably 100% by mass or less. The content of the structural units derived from a styrene compound is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 5 to 80% by mass, based on all the structural units of the copolymer. The content of the structural units derived from the (meth)acrylic compound is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20 to 95% by mass, based on all structural units of the copolymer.

[0054] In terms of achieving better effects of the present invention, the binder polymer preferably has an aromatic ring structure, and more preferably has a constituent unit having an aromatic ring structure. Examples of monomers that form structural units having an aromatic ring structure include styrene compounds such as styrene, tert-butoxystyrene, methylstyrene, and α-methylstyrene, as well as benzyl (meth)acrylate. Of these, styrene compounds are preferred, and styrene is more preferred. In addition, the binder polymer more preferably has a structural unit represented by the following formula (S) (a structural unit derived from styrene), in terms of achieving better effects of the present invention.

[0055] [ka]

[0056] When the binder polymer has a structural unit having an aromatic ring structure, the content of the structural unit having an aromatic ring structure is preferably 5 to 90 mass%, more preferably 10 to 70 mass%, and further preferably 20 to 60 mass%, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, the content of the structural unit having an aromatic ring structure in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 60 mol %, and even more preferably 20 to 60 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. Furthermore, the content of the structural unit represented by the above formula (S) in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 60 mol %, and even more preferably 20 to 60 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In the present disclosure, when the content of the "structural unit" is specified by a molar ratio, the "structural unit" is synonymous with the "monomer unit". In the present disclosure, the "monomer unit" may be modified after polymerization by a polymer reaction or the like. The same applies hereinafter.

[0057] In order to obtain a more excellent effect of the present invention, the binder polymer preferably has a monocyclic aliphatic hydrocarbon ring structure or a polycyclic aliphatic hydrocarbon ring structure. In other words, the binder polymer preferably has a structural unit having a monocyclic or polycyclic aliphatic hydrocarbon ring structure. In particular, the binder polymer more preferably has a polycyclic aliphatic hydrocarbon ring structure, and even more preferably has a ring structure in which two or more aliphatic hydrocarbon rings are condensed.

[0058] Examples of the ring that constitutes the aliphatic hydrocarbon ring structure in the structural unit having an aliphatic hydrocarbon ring structure include a tricyclodecane ring, a cyclohexane ring, a cyclopentane ring, a norbornane ring, and an isoborone ring. Among these, in terms of superior effects of the present invention, a ring in which two or more aliphatic hydrocarbon rings are condensed is preferred, and a tetrahydrodicyclopentadiene ring (tricyclo[5.2.1.0 2,6 ]decane ring) is more preferred. Examples of monomers that form a structural unit having an aliphatic hydrocarbon ring structure include dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. In addition, in terms of better effects of the present invention, the binder polymer more preferably has a structural unit represented by the following formula (Cy), and more preferably has a structural unit represented by the above formula (S) and a structural unit represented by the following formula (Cy).

[0059] [ka]

[0060] In the formula (Cy), R M represents a hydrogen atom or a methyl group, R Cy represents a monovalent group having an aliphatic hydrocarbon ring structure.

[0061] R in formula (Cy) M is preferably a methyl group. R in formula (Cy) Cy is preferably a monovalent group having an aliphatic hydrocarbon ring structure having 5 to 20 carbon atoms, more preferably a monovalent group having an aliphatic hydrocarbon ring structure having 6 to 16 carbon atoms, and even more preferably a monovalent group having an aliphatic hydrocarbon ring structure having 8 to 14 carbon atoms, in terms of better effects of the present invention. In addition, R in formula (Cy) Cy The aliphatic hydrocarbon ring structure in may be a monocyclic aliphatic hydrocarbon ring structure or a polycyclic aliphatic hydrocarbon ring structure. Among them, from the viewpoint of more excellent effects of the present invention, a monocyclic aliphatic hydrocarbon ring structure such as a cyclopentane ring structure, a cyclohexane ring structure, or an isoborone ring structure, or a polycyclic aliphatic hydrocarbon ring structure such as a tetrahydrodicyclopentadiene ring structure or a norbornane ring structure is preferable, a cyclohexane ring structure or a tetrahydrodicyclopentadiene ring structure is more preferable, and a tetrahydrodicyclopentadiene ring structure is even more preferable. Furthermore, R in formula (Cy) Cy In terms of achieving better effects of the present invention, the aliphatic hydrocarbon ring structure in is preferably a polycyclic aliphatic hydrocarbon ring, more preferably a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and even more preferably a ring in which two to four aliphatic hydrocarbon rings are condensed. Furthermore, R in formula (Cy) CyIn terms of achieving better effects of the present invention, is preferably a group in which the oxygen atom of -C(=O)O- in formula (Cy) is directly bonded to an aliphatic hydrocarbon ring structure (which may be monocyclic or polycyclic), i.e., an aliphatic hydrocarbon ring group, more preferably a cyclohexyl group or a dicyclopentanyl group, and even more preferably a dicyclopentanyl group.

[0062] The binder polymer may have one type of structural unit having an aliphatic hydrocarbon ring structure, or may have two or more types of structural units having an aliphatic hydrocarbon ring structure. When the binder polymer has a structural unit having an aliphatic hydrocarbon ring structure, the content of the structural unit having an aliphatic hydrocarbon ring structure is preferably 5 to 90 mass%, more preferably 10 to 80 mass%, and even more preferably 20 to 70 mass%, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, the content of the structural unit having an aliphatic hydrocarbon ring structure in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 60 mol %, and even more preferably 20 to 50 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. Furthermore, the content of the structural unit represented by the above formula (Cy) in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 60 mol %, and even more preferably 20 to 50 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention.

[0063] When the binder polymer has a structural unit having an aromatic ring structure and a structural unit having an aliphatic hydrocarbon ring structure, the total content of the structural units having an aromatic ring structure and the structural units having an aliphatic hydrocarbon ring structure is preferably 10 to 90 mass%, more preferably 20 to 80 mass%, and even more preferably 40 to 75 mass%, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, the total content of the structural units having an aromatic ring structure and the structural units having an aliphatic hydrocarbon ring structure in the binder polymer is preferably 10 to 80 mol %, more preferably 20 to 70 mol %, and even more preferably 40 to 60 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. Furthermore, the total content of the structural unit represented by the above formula (S) and the structural unit represented by the above formula (Cy) in the binder polymer is preferably 10 to 80 mol %, more preferably 20 to 70 mol %, and even more preferably 40 to 60 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, in order to obtain better effects of the present invention, it is preferable that the molar amount nS of the structural unit represented by the above formula (S) in the binder polymer and the molar amount nCy of the structural unit represented by the above formula (Cy) satisfy the relationship shown in the following formula (SCy), more preferably the relationship shown in the following formula (SCy-1), and even more preferably the relationship shown in the following formula (SCy-2). 0.2≦nS / (nS+nCy)≦0.8 Formula (SCy) 0.30≦nS / (nS+nCy)≦0.75 Formula (SCy-1) 0.40≦nS / (nS+nCy)≦0.70 Formula (SCy-2)

[0064] The binder polymer preferably has a structural unit having an acid group, in that the effects of the present invention are more excellent. Examples of the acid group include a carboxy group, a sulfo group, a phosphonic acid group, and a phosphoric acid group, with the carboxy group being preferred. As the structural unit having an acid group, a structural unit derived from (meth)acrylic acid shown below is preferred, and a structural unit derived from methacrylic acid is more preferred.

[0065] [ka]

[0066] The binder polymer may have one type of structural unit having an acid group alone, or may have two or more types of structural units having an acid group. When the binder polymer has a structural unit having an acid group, the content of the structural unit having an acid group is preferably 5 to 50 mass%, more preferably 5 to 40 mass%, and even more preferably 10 to 30 mass%, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, the content of the structural unit having an acid group in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 50 mol %, and even more preferably 20 to 40 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention. Further, the content of the (meth)acrylic acid-derived structural units in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 50 mol %, and even more preferably 20 to 40 mol %, based on the total structural units of the binder polymer, in terms of better effects of the present invention.

[0067] In terms of achieving better effects of the present invention, the binder polymer preferably has a reactive group, and more preferably has a structural unit having a reactive group. The reactive group is preferably a radically polymerizable group, more preferably an ethylenically unsaturated group. In addition, when the binder polymer has an ethylenically unsaturated group, the binder polymer preferably has a structural unit having an ethylenically unsaturated group in a side chain. In the present disclosure, the term "main chain" refers to the relatively longest bonding chain in the molecule of the polymer compound that constitutes the resin, and the term "side chain" refers to an atomic group branching off from the main chain. The ethylenically unsaturated group is preferably a (meth)acrylic group, more preferably a (meth)acryloxy group. Examples of structural units having a reactive group include, but are not limited to, those shown below.

[0068] [ka]

[0069] The binder polymer may have one type of structural unit having a reactive group, or may have two or more types of structural units having a reactive group. When the binder polymer has a structural unit having a reactive group, the content of the structural unit having a reactive group is preferably 5 to 70 mass%, more preferably 10 to 50 mass%, and even more preferably 20 to 40 mass%, based on the total structural units of the binder polymer, in terms of better effects of the present invention. In addition, the content of the structural unit having a reactive group in the binder polymer is preferably 5 to 70 mol %, more preferably 10 to 60 mol %, and even more preferably 20 to 50 mol %, based on the total structural units of the binder polymer, in order to obtain better effects of the present invention.

[0070] Examples of a method for introducing a reactive group into a binder polymer include a method in which a functional group such as a hydroxy group, a carboxy group, a primary amino group, a secondary amino group, an acetoacetyl group, or a sulfo group is reacted with a compound such as an epoxy compound, a blocked isocyanate compound, an isocyanate compound, a vinyl sulfone compound, an aldehyde compound, a methylol compound, or a carboxylic acid anhydride. A preferred example of a method for introducing a reactive group into a binder polymer is to synthesize a polymer having a carboxy group by polymerization, and then react a part of the carboxy group of the obtained polymer with glycidyl (meth)acrylate by a polymer reaction to introduce a (meth)acryloxy group into the polymer. By this method, a binder polymer having a (meth)acryloxy group in the side chain can be obtained. The polymerization reaction is preferably carried out at a temperature of 70 to 100° C., more preferably at a temperature of 80 to 90° C. The polymerization initiator used in the polymerization reaction is preferably an azo-based initiator, more preferably V-601 (trade name) or V-65 (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The polymer reaction is preferably carried out at a temperature of 80 to 110° C. In the polymer reaction, a catalyst such as an ammonium salt is preferably used.

[0071] As the binder polymer, the following polymers are preferred in terms of achieving better effects of the present invention: The content ratios (a to d) of each of the structural units shown below and the weight average molecular weight Mw can be appropriately changed depending on the purpose.

[0072] [ka]

[0073] [ka]

[0074] The binder polymer may also contain a polymer having a structural unit with a carboxylic acid anhydride structure (hereinafter, also referred to as "polymer X"). The carboxylic acid anhydride structure may be either a chain carboxylic acid anhydride structure or a cyclic carboxylic acid anhydride structure, but is preferably a cyclic carboxylic acid anhydride structure. The ring of the cyclic carboxylic acid anhydride structure is preferably a 5- to 7-membered ring, more preferably a 5- or 6-membered ring, and even more preferably a 5-membered ring.

[0075] The structural unit having a carboxylic acid anhydride structure is preferably a structural unit containing a divalent group obtained by removing two hydrogen atoms from a compound represented by the following formula P-1 in its main chain, or a structural unit in which a monovalent group obtained by removing one hydrogen atom from a compound represented by the following formula P-1 is bonded to the main chain directly or via a divalent linking group.

[0076] [ka]

[0077] In formula P-1, R A1a represents a substituent, n 1a R A1a may be the same or different, Z 1a represents a divalent group forming a ring containing -C(=O)-OC(=O)-, n 1arepresents an integer greater than or equal to 0.

[0078] R A1a Examples of the substituent represented by the formula (I) include an alkyl group. Z 1a As the alkylene group, an alkylene group having 2 to 4 carbon atoms is preferable, an alkylene group having 2 or 3 carbon atoms is more preferable, and an alkylene group having 2 carbon atoms is even more preferable. n 1a represents an integer equal to or greater than 0. 1a When represents an alkylene group having 2 to 4 carbon atoms, n 1a is preferably an integer of 0 to 4, more preferably an integer of 0 to 2, and even more preferably 0. n 1a If represents an integer of 2 or more, there are multiple R A1a may be the same or different. In addition, if there are multiple R A1a may be bonded to each other to form a ring, but preferably do not bond to each other to form a ring.

[0079] As a structural unit having a carboxylic acid anhydride structure, a structural unit derived from an unsaturated carboxylic acid anhydride is preferable, a structural unit derived from an unsaturated cyclic carboxylic acid anhydride is more preferable, a structural unit derived from an unsaturated aliphatic cyclic carboxylic acid anhydride is even more preferable, a structural unit derived from maleic anhydride or itaconic anhydride is particularly preferable, and a structural unit derived from maleic anhydride is most preferable.

[0080] Specific examples of structural units having a carboxylic acid anhydride structure are given below, but the structural units having a carboxylic acid anhydride structure are not limited to these specific examples. In the following structural units, Rx represents a hydrogen atom, a methyl group, a CH2OH group, or a CF3 group, and Me represents a methyl group.

[0081] [ka]

[0082] [ka]

[0083] The structural unit having a carboxylic acid anhydride structure in the polymer X may be of one type alone, or of two or more types.

[0084] The total content of the structural units having a carboxylic acid anhydride structure relative to all the structural units of the polymer X is preferably from 0 to 60 mol %, more preferably from 5 to 40 mol %, and even more preferably from 10 to 35 mol %.

[0085] The photosensitive composition layer may contain only one type of polymer X, or may contain two or more types. When the photosensitive composition layer contains polymer X, the content of polymer X is preferably 0.10 to 30.00 mass%, more preferably 0.20 to 20.00 mass%, further preferably 0.20 to 5.00 mass%, and particularly preferably 0.50 to 1.50 mass%, relative to the total mass of the photosensitive composition layer, in order to obtain better effects of the present invention.

[0086] The weight average molecular weight (Mw) of the binder polymer is preferably 5,000 or more, more preferably 10,000 or more, further preferably from 10,000 to 50,000, and particularly preferably from 10,000 to 30,000, in terms of achieving better effects of the present invention. The dispersity of the binder polymer (weight average molecular weight Mw / number average molecular weight Mn) is preferably from 1.0 to 3.0, and more preferably from 2.0 to 3.0, from the viewpoint of reducing development residues.

[0087] The acid value of the binder polymer is preferably from 10 to 200 mgKOH / g, more preferably from 60 to 200 mgKOH / g, further preferably from 60 to 150 mgKOH / g, and particularly preferably from 60 to 110 mgKOH / g. The acid value of the binder polymer is a value measured according to the method described in JIS K0070:1992.

[0088] The photosensitive composition layer may contain only one type of binder polymer, or may contain two or more types of binder polymer. The content of the binder polymer is preferably from 10.00 to 90.00 mass %, more preferably from 30.00 to 80.00 mass %, further preferably from 40.00 to 70.00 mass %, and particularly preferably from 45.00 to 60.00 mass %, relative to the total mass of the photosensitive composition layer, in terms of better effects of the present invention.

[0089] [Polymerization initiator] The photosensitive composition layer may contain a polymerization initiator. The polymerization initiator is not particularly limited, and any known polymerization initiator can be used. As the polymerization initiator, a photopolymerization initiator is preferable. Examples of the polymerization initiator include a photopolymerization initiator having an oxime ester structure (hereinafter also referred to as an "oxime-based photopolymerization initiator"), a photopolymerization initiator having an α-aminoalkylphenone structure (hereinafter also referred to as an "α-aminoalkylphenone-based photopolymerization initiator"), a photopolymerization initiator having an α-hydroxyalkylphenone structure (hereinafter also referred to as an "α-hydroxyalkylphenone-based polymerization initiator"), a photopolymerization initiator having an acylphosphine oxide structure (hereinafter also referred to as an "acylphosphine oxide-based photopolymerization initiator"), and a photopolymerization initiator having an N-phenylglycine structure (hereinafter also referred to as an "N-phenylglycine-based photopolymerization initiator").

[0090] The polymerization initiator preferably contains at least one selected from the group consisting of an oxime-based photopolymerization initiator, an α-aminoalkylphenone-based photopolymerization initiator, an α-hydroxyalkylphenone-based polymerization initiator, and an N-phenylglycine-based photopolymerization initiator, more preferably contains at least one selected from the group consisting of an oxime-based photopolymerization initiator, an α-aminoalkylphenone-based photopolymerization initiator, and an N-phenylglycine-based photopolymerization initiator, and even more preferably contains at least one selected from the group consisting of an oxime-based photopolymerization initiator and an α-aminoalkylphenone-based photopolymerization initiator.

[0091] Examples of the polymerization initiator include those described in paragraphs

[0031] to

[0042] of JP-A-2011-95716 and paragraphs

[0064] to

[0081] of JP-A-2015-014783.

[0092] Examples of the polymerization initiator include 1-[4-(phenylthio)]phenyl-1,2-octanedione-2-(O-benzoyloxime) [trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) [trade name: IRGACURE (registered trademark) OXE-02, manufactured by BASF], 8-[5-(2,4,6-trimethylphenyl)-11-(2- ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) [trade name: IRGACURE® OXE-03, manufactured by BASF], 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methyl-1-pentanone-1-(O-acetyloxime) [trade name: IRGACURE® OXE-04, manufactured by BASF], oxime ester Compounds of the series (trade name: Lunar (registered trademark) 6, manufactured by DKSH Japan Co., Ltd.), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-305, manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazol-3-yl]-, 2-(O-acetyloxime) (trade name: TR-PBG-326, manufactured by Changzhou Strong Electronic New Materials Co., Ltd.), Changzhou Strong Electronic New Materials Co., Ltd.), 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-391, Changzhou Strong Electronic New Materials Co., Ltd.), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad® 379EG, IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad® 907, IGM Resins BV)2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)benzyl]phenyl}-2-methylpropan-1-one [trade name: Omnirad® 127, manufactured by IGM Resins BV], 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 [trade name: Omnirad® 369, manufactured by IGM Resins BV], 2-hydroxy-2-methyl-1-phenyl-propan-1-one [trade name: Omnirad® 1173, manufactured by IGM Resins BV], 1-hydroxycyclohexyl phenyl ketone [trade name: Omnirad® 184, manufactured by IGM Resins BV], 2,2-dimethoxy-1,2-diphenylethane-1-one [trade name: Omnirad® 651, manufactured by IGM Resins BV] BV), 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, and 1-(biphenyl-4-yl)-2-methyl-2-morpholinopropan-1-one (trade name: APi-307, Shenzhen UV-ChemTech Ltd.).

[0093] The polymerization initiator may be used alone or in combination of two or more kinds. The content of the polymerization initiator in the photosensitive composition layer is not particularly limited, but is preferably 0.10% by mass or more, more preferably 0.50% by mass or more, based on the total mass of the photosensitive composition layer. The upper limit is not particularly limited, but is preferably 10.00% by mass or less, more preferably 5.00% by mass or less, based on the total mass of the photosensitive composition layer.

[0094] [Polymerizable compound] The photosensitive composition layer may contain a polymerizable compound. The polymerizable compound is a compound having a polymerizable group. Examples of the polymerizable group include a radical polymerizable group and a cationic polymerizable group, and the radical polymerizable group is preferable.

[0095] The polymerizable compound preferably contains a radically polymerizable compound having an ethylenically unsaturated group (hereinafter, also simply referred to as an "ethylenically unsaturated compound"). The ethylenically unsaturated group is preferably a (meth)acryloxy group. In this specification, the ethylenically unsaturated compound is a compound other than the above-mentioned binder polymer, and preferably has a molecular weight of less than 5,000.

[0096] As the polymerizable compound, a compound represented by the following formula (M) (also simply referred to as "compound M") is preferable. Q 2 -R 1a -Q 1 Formula (M) In formula (M), Q 1 and Q 2 each independently represents a (meth)acryloyloxy group; R 1 represents a divalent linking group having a chain structure.

[0097] Q in formula (M) 1 and Q 2 From the viewpoint of ease of synthesis, Q 1 and Q 2 are preferably the same group. In addition, Q in formula (M) 1 and Q 2 is preferably an acryloyloxy group from the viewpoint of reactivity. R in formula (M) 1a In terms of the effects of the present invention, an alkylene group, an alkyleneoxyalkylene group (-L 1 -OL 1 -), or a polyalkyleneoxyalkylene group (-(L 1 -O) p -L 1 -) is preferred, a hydrocarbon group having 2 to 20 carbon atoms or a polyalkyleneoxyalkylene group is more preferred, an alkylene group having 4 to 20 carbon atoms is further preferred, and a linear alkylene group having 6 to 18 carbon atoms is particularly preferred. The hydrocarbon group may have a chain structure at least in a portion thereof, and the portion other than the chain structure is not particularly limited and may be, for example, a branched, cyclic, or linear alkylene group having 1 to 5 carbon atoms, an arylene group, an ether bond, or a combination thereof. An alkylene group or a group combining two or more alkylene groups and one or more arylene groups is preferable, an alkylene group is more preferable, and a linear alkylene group is even more preferable. In addition, the above L 1 each independently represents an alkylene group, preferably an ethylene group, a propylene group, or a butylene group, and more preferably an ethylene group or a 1,2-propylene group. p represents an integer of 2 or more, preferably an integer of 2 to 10.

[0098] In addition, Q in compound M 1 and Q 2 The number of atoms in the shortest linking chain between and is preferably 3 to 50, more preferably 4 to 40, even more preferably 6 to 20, and particularly preferably 8 to 12, in terms of achieving better effects of the present invention. In this disclosure, 1 and Q 2 The number of atoms in the shortest chain connecting Q 1 R to be connected 1 Q from atoms in 2 R to be connected 1 is the shortest number of atoms that can connect to an atom in

[0099] Examples of the compound M include 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, hydrogenated bisphenol F di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. The above ester monomers may also be used as mixtures. Among these, in terms of better effects of the present invention, compound M is preferably at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate, more preferably at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate, and even more preferably at least one compound selected from the group consisting of 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate.

[0100] As the polymerizable compound, an ethylenically unsaturated compound having two or more functionalities is preferable. In this specification, the term "di- or higher functional ethylenically unsaturated compound" means a compound having two or more ethylenically unsaturated groups in one molecule. As the ethylenically unsaturated group in the ethylenically unsaturated compound, a (meth)acryloyl group is preferred. As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred.

[0101] The difunctional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of the difunctional ethylenically unsaturated compound other than the compound M include tricyclodecane dimethanol di(meth)acrylate and tricyclodecane dimenanol di(meth)acrylate. The difunctional ethylenically unsaturated compound preferably includes a polymerizable compound B1 having an aromatic ring and two ethylenically unsaturated groups.

[0102] When the photosensitive composition layer contains the polymerizable compound B1, the mass ratio of the content of the polymerizable compound B1 to the total mass of the polymerizable compounds is preferably 40% or more, more preferably 50% or more, even more preferably 55% or more, and particularly preferably 60% or more, from the viewpoint of better resolution. The upper limit is not particularly limited, but is, for example, 100% or less, preferably 99% or less, more preferably 95% or less, even more preferably 90% or less, and particularly preferably 85% or less, from the viewpoint of peelability.

[0103] The aromatic ring of the polymerizable compound B1 includes, for example, aromatic hydrocarbon rings such as benzene ring, naphthalene ring and anthracene ring, aromatic heterocycles such as thiophene ring, furan ring, pyrrole ring, imidazole ring, triazole ring and pyridine ring, and condensed rings thereof, and is preferably aromatic hydrocarbon ring, more preferably benzene ring.The aromatic ring may have a substituent. The polymerizable compound B1 may have only one aromatic ring, or may have two or more aromatic rings.

[0104] The polymerizable compound B1 preferably has a bisphenol structure from the viewpoint of improving the resolution by suppressing swelling of the photosensitive composition layer due to a developer. Examples of the bisphenol structure include a bisphenol A structure derived from bisphenol A (2,2-bis(4-hydroxyphenyl)propane), a bisphenol F structure derived from bisphenol F (2,2-bis(4-hydroxyphenyl)methane), and a bisphenol B structure derived from bisphenol B (2,2-bis(4-hydroxyphenyl)butane), with the bisphenol A structure being preferred.

[0105] An example of the polymerizable compound B1 having a bisphenol structure is a compound having a bisphenol structure and two polymerizable groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure. Both ends of the bisphenol structure may be directly bonded to the two polymerizable groups, or may be bonded via one or more alkyleneoxy groups. The alkyleneoxy groups added to both ends of the bisphenol structure are preferably ethyleneoxy or propyleneoxy, more preferably ethyleneoxy. The number of alkyleneoxy groups added to the bisphenol structure is not particularly limited, but is preferably 4 to 16, more preferably 6 to 14 per molecule. The polymerizable compound B1 having a bisphenol structure is described in paragraphs 0072 to 0080 of JP2016-224162A, the contents of which are incorporated herein by reference.

[0106] As the polymerizable compound B1, a bifunctional ethylenically unsaturated compound having a bisphenol A structure is preferable, and 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane is more preferable. Examples of 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (FA-324M, Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxyethoxypropoxy)phenyl)propane, 2,2-bis(4-(methacryloxypentaethoxy)phenyl)propane (BPE-500, Shin-Nakamura Chemical Co., Ltd.), and 2,2-bis(4-(methacryloxydodecaethoxy)phenyl)propane. Examples of the ethoxylated (10) bisphenol A diacrylate include 2,2-bis(4-(methacryloxytetrapropoxy)phenyl)propane (FA-3200MY, manufactured by Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxypentadecaethoxy)phenyl)propane (BPE-1300, manufactured by Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (BPE-200, manufactured by Shin-Nakamura Chemical Co., Ltd.), and ethoxylated (10) bisphenol A diacrylate (NK Ester A-BPE-10, manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0107] As the polymerizable compound B1, a compound represented by the following general formula (B1) is also preferred.

[0108] [ka]

[0109] In the general formula B1, R1 and R2 each independently represent a hydrogen atom or a methyl group. A represents C2H4. B represents C3H6. n1 and n3 each independently represent an integer of 1 to 39, and n1+n3 represents an integer of 2 to 40. n2 and n4 each independently represent an integer of 0 to 29, and n2+n4 represents an integer of 0 to 30. The arrangement of the structural units -(AO)- and -(BO)- may be random or block. In the case of a block, either -(AO)- or -(BO)- may be on the bisphenyl group side. In one embodiment, n1+n2+n3+n4 is preferably an integer of 2 to 20, more preferably an integer of 2 to 16, and even more preferably an integer of 4 to 12. Furthermore, n2+n4 is preferably an integer of 0 to 10, more preferably an integer of 0 to 4, even more preferably an integer of 0 to 2, and particularly preferably 0.

[0110] The polymerizable compound B1 may be used alone or in combination of two or more kinds. When the photosensitive composition layer contains the polymerizable compound B1, the content is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the photosensitive composition layer, from the viewpoint of better resolution. The upper limit is not particularly limited, but is preferably 70% by mass or less, more preferably 60% by mass or less, from the viewpoint of transferability and edge fusion (phenomenon in which the photosensitive resin oozes out from the edge of the transfer member).

[0111] Commercially available bifunctional ethylenically unsaturated compounds include, for example, tricyclodecane dimethanol diacrylate (trade name: NK Ester A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimenanol dimethacrylate (trade name: NK Ester DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (trade name: NK Ester A-NOD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (trade name: NK Ester A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0112] The tri- or higher functional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of the tri- or higher functional ethylenically unsaturated compound include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds having a glycerin tri(meth)acrylate skeleton.

[0113] Here, "(tri / tetra / penta / hexa)(meth)acrylate" is a concept that encompasses tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, and hexa(meth)acrylate, and "(tri / tetra)(meth)acrylate" is a concept that encompasses tri(meth)acrylate and tetra(meth)acrylate.

[0114] Examples of the polymerizable compound include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., and A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD (registered trademark) R-604 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., and EBECRYL (registered trademark) 135 manufactured by Daicel-Allnex Co., Ltd., etc.), and ethoxylated glycerin triacrylate (NK Ester A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd., etc.).

[0115] The polymerizable compound also includes a urethane (meth)acrylate compound (preferably a tri- or higher functional urethane (meth)acrylate compound). Examples of trifunctional or higher urethane (meth)acrylate compounds include 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.), NK Ester UA-32P (manufactured by Shin-Nakamura Chemical Co., Ltd.), and NK Ester UA-1100H (manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0116] The polymerizable compound is preferably an ethylenically unsaturated compound having an acid group. Examples of acid groups include phosphate groups, sulfo groups, and carboxy groups. Of these, the acid group is preferably a carboxy group. Examples of the ethylenically unsaturated compound having an acid group include a tri- or tetrafunctional ethylenically unsaturated compound having an acid group [a carboxy group has been introduced into a pentaerythritol tri- or tetraacrylate (PETA) skeleton (acid value: 80 to 120 mg KOH / g)] and a penta- or hexafunctional ethylenically unsaturated compound having an acid group [a carboxy group has been introduced into a dipentaerythritol penta- or hexaacrylate (DPHA) skeleton (acid value: 25 to 70 mg KOH / g)]. These trifunctional or higher ethylenically unsaturated compounds having an acid group may be used in combination with a difunctional ethylenically unsaturated compound having an acid group, if necessary.

[0117] The ethylenically unsaturated compound having an acid group is preferably at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof. When the ethylenically unsaturated compound having an acid group is at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof, the developability and film strength are further improved. The di- or higher functional ethylenically unsaturated compound having a carboxy group is not particularly limited and can be appropriately selected from known compounds. Examples of the difunctional or higher ethylenically unsaturated compound having a carboxy group include ARONIX (registered trademark) TO-2349 (manufactured by Toagosei Co., Ltd.), ARONIX (registered trademark) M-520 (manufactured by Toagosei Co., Ltd.), and ARONIX (registered trademark) M-510 (manufactured by Toagosei Co., Ltd.).

[0118] As the ethylenically unsaturated compound having an acid group, the polymerizable compound having an acid group described in paragraphs

[0025] to

[0030] of JP-A-2004-239942 is preferred, and the contents of this publication are incorporated herein by reference.

[0119] Examples of the polymerizable compound include compounds obtained by reacting a polyhydric alcohol with an α,β-unsaturated carboxylic acid, compounds obtained by reacting a glycidyl group-containing compound with an α,β-unsaturated carboxylic acid, urethane monomers such as (meth)acrylate compounds having a urethane bond, phthalic acid compounds such as γ-chloro-β-hydroxypropyl-β'-(meth)acryloyloxyethyl-o-phthalate, β-hydroxyethyl-β'-(meth)acryloyloxyethyl-o-phthalate, and β-hydroxypropyl-β'-(meth)acryloyloxyethyl-o-phthalate, and (meth)acrylic acid alkyl esters. These may be used alone or in combination of two or more.

[0120] Examples of compounds obtained by reacting a polyhydric alcohol with an α,β-unsaturated carboxylic acid include bisphenol A-based (meth)acrylate compounds such as 2,2-bis(4-((meth)acryloxypolyethoxy)phenyl)propane, 2,2-bis(4-((meth)acryloxypolypropoxy)phenyl)propane, and 2,2-bis(4-((meth)acryloxypolyethoxypolypropoxy)phenyl)propane; polyethylene glycol di(meth)acrylates having 2 to 14 ethylene oxide groups; polypropylene glycol di(meth)acrylates having 2 to 14 propylene oxide groups; polyethylene polypropylene glycol di(meth)acrylates having 2 to 14 ethylene oxide groups and 2 to 14 propylene oxide groups; trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane diethoxy tri(meth)acrylate, trimethylolpropane triethoxy tri(meth)acrylate, trimethylolpropane tetraethoxy tri(meth)acrylate, trimethylolpropane pentaethoxy tri(meth)acrylate, di(trimethylolpropane) tetraacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among these, the above compound is preferably an ethylenically unsaturated compound having a tetramethylolmethane structure or a trimethylolpropane structure, and more preferably tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, or di(trimethylolpropane)tetraacrylate.

[0121] Examples of the polymerizable compound include caprolactone-modified compounds of ethylenically unsaturated compounds (e.g., KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., and A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd.), alkylene oxide-modified compounds of ethylenically unsaturated compounds (e.g., KAYARAD R-604 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., and EBECRYL (registered trademark) 135 manufactured by Daicel-Allnex Corporation), and ethoxylated glycerin triacrylate (A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0122] Among these, as the polymerizable compound (particularly, an ethylenically unsaturated compound), one containing an ester bond is also preferred in terms of excellent developability of the photosensitive composition layer after transfer. The ethylenically unsaturated compound containing an ester bond is not particularly limited as long as it contains an ester bond in the molecule, but in terms of excellent effects of the present invention, an ethylenically unsaturated compound having a tetramethylolmethane structure or a trimethylolpropane structure is preferred, and tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, or di(trimethylolpropane)tetraacrylate is more preferred. From the viewpoint of imparting reliability, the ethylenically unsaturated compound preferably contains an ethylenically unsaturated compound having an aliphatic group having 6 to 20 carbon atoms and the above-mentioned ethylenically unsaturated compound having a tetramethylolmethane structure or a trimethylolpropane structure. Examples of ethylenically unsaturated compounds having an aliphatic structure with 6 or more carbon atoms include 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate.

[0123] The polymerizable compound may, for example, be a polymerizable compound having an aliphatic hydrocarbon ring structure (preferably a bifunctional ethylenically unsaturated compound). The polymerizable compound is preferably a polymerizable compound having a ring structure in which two or more aliphatic hydrocarbon rings are condensed (preferably a structure selected from the group consisting of a tricyclodecane structure and a tricyclodecene structure), more preferably a bifunctional ethylenically unsaturated compound having a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and even more preferably tricyclodecane dimethanol di(meth)acrylate. As the aliphatic hydrocarbon ring structure, a cyclopentane structure, a cyclohexane structure, a tricyclodecane structure, a tricyclodecene structure, a norbornane structure, or an isoborone structure is preferred in terms of achieving superior effects of the present invention.

[0124] The molecular weight of the polymerizable compound is preferably from 200 to 3,000, more preferably from 250 to 2,600, further preferably from 280 to 2,200, and particularly preferably from 300 to 2,200. Among the polymerizable compounds contained in the photosensitive composition layer, the content ratio of polymerizable compounds having a molecular weight of 300 or less is preferably 30 mass % or less, more preferably 25 mass % or less, and even more preferably 20 mass % or less, based on the content of all polymerizable compounds contained in the photosensitive composition layer. The lower limit of the content of the polymerizable compound having a molecular weight of 300 or less is not particularly limited, but is preferably 1.0 mass % or more.

[0125] The photosensitive composition layer preferably contains a difunctional or higher ethylenically unsaturated compound, more preferably contains a trifunctional or higher ethylenically unsaturated compound, and further preferably contains a trifunctional or tetrafunctional ethylenically unsaturated compound.

[0126] The photosensitive composition layer also preferably contains a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, and a binder polymer having a structural unit having an aliphatic hydrocarbon ring.

[0127] The photosensitive composition layer preferably contains a compound represented by formula (M) and an ethylenically unsaturated compound having an acid group, more preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, and further preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a succinic acid modified product of dipentaerythritol pentaacrylate.

[0128] The photosensitive composition layer preferably contains a compound represented by formula (M), an ethylenically unsaturated compound having an acid group, and a thermally crosslinkable compound described later, and more preferably contains a compound represented by formula (M), an ethylenically unsaturated compound having an acid group, and a blocked isocyanate compound described later.

[0129] The photosensitive composition layer preferably contains a difunctional ethylenically unsaturated compound (preferably a difunctional (meth)acrylate compound) and a tri- or higher functional ethylenically unsaturated compound (preferably a tri- or higher functional (meth)acrylate compound).

[0130] From the viewpoint of rust prevention, the photosensitive composition layer preferably contains a compound M and a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure.

[0131] From the viewpoints of adhesion, suppression of development residues, and rust prevention, the photosensitive composition layer preferably contains a compound M, and an ethylenically unsaturated compound having an acid group, more preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, and an ethylenically unsaturated compound having an acid group, still more preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, and an ethylenically unsaturated compound having an acid group, and particularly preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, an ethylenically unsaturated compound having an acid group, and a urethane (meth)acrylate compound.

[0132] From the viewpoints of adhesion, suppression of development residue, and rust prevention, the photosensitive composition layer preferably contains 1,9-nonanediol diacrylate and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, more preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, further preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, dipentaerythritol hexaacrylate (A-DPH), and an ethylenically unsaturated compound having a carboxylic acid group, and particularly preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, an ethylenically unsaturated compound having a carboxylic acid group, and a urethane acrylate compound.

[0133] The photosensitive composition layer may contain a monofunctional ethylenically unsaturated compound as the ethylenically unsaturated compound. The content of the di- or higher functional ethylenically unsaturated compound in the above ethylenically unsaturated compound is preferably 60 to 100 mass %, more preferably 80 to 100 mass %, and even more preferably 90 to 100 mass %, based on the total content of all ethylenically unsaturated compounds contained in the photosensitive composition layer.

[0134] The polymerizable compound (particularly, the ethylenically unsaturated compound) may be used alone or in combination of two or more kinds. The content of the polymerizable compound (particularly, the ethylenically unsaturated compound) in the photosensitive composition layer is preferably 1.00 to 70.00 mass %, more preferably 10.00 to 70.00 mass %, even more preferably 15.0 to 50.0 mass %, and particularly preferably 20.0 to 40.0 mass %, relative to the total mass of the photosensitive composition layer.

[0135] [Heterocyclic compounds] The photosensitive composition layer may contain a heterocyclic compound. The heterocycle contained in the heterocyclic compound may be either a monocyclic or polycyclic heterocycle. Examples of heteroatoms contained in the heterocyclic compound include a nitrogen atom, an oxygen atom, and a sulfur atom. The heterocyclic compound preferably contains at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom, and more preferably contains a nitrogen atom.

[0136] Examples of heterocyclic compounds include triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, benzoxazole compounds, pyrimidine compounds, and pyridine compounds. Among them, the heterocyclic compound is preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzimidazole compounds, benzoxazole compounds, and pyridine compounds, and more preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, and benzoxazole compounds.

[0137] Preferable specific examples of the heterocyclic compound are shown below. Examples of the triazole compound and benzotriazole compound include the following compounds.

[0138] [ka]

[0139] [ka]

[0140] Examples of the tetrazole compound include the following compounds.

[0141] [ka]

[0142] [ka]

[0143] Examples of the thiadiazole compound include the following compounds.

[0144] [ka]

[0145] Examples of the triazine compound include the following compounds.

[0146] [ka]

[0147] Examples of rhodanine compounds include the following compounds.

[0148] [ka]

[0149] Examples of the thiazole compound include the following compounds.

[0150] [ka]

[0151] Examples of the benzothiazole compound include the following compounds.

[0152] [ka]

[0153] Examples of the benzimidazole compound include the following compounds.

[0154] [ka]

[0155] [ka]

[0156] Examples of the benzoxazole compound include the following compounds.

[0157] [ka]

[0158] Examples of the pyridine compound include (iso)nicotinic acid and (iso)nicotinamide.

[0159] The photosensitive composition layer may contain one kind of heterocyclic compound alone, or may contain two or more kinds of heterocyclic compounds. When the photosensitive composition layer contains a heterocyclic compound, the content of the heterocyclic compound is preferably 0.01 to 20.00 mass%, more preferably 0.10 to 10.00 mass%, still more preferably 0.10 to 5.00 mass%, and particularly preferably 0.10 to 1.00 mass%, relative to the total mass of the photosensitive composition layer.

[0160] [Aliphatic thiol compounds] The photosensitive composition layer may contain an aliphatic thiol compound.

[0161] As the aliphatic thiol compound, a monofunctional aliphatic thiol compound or a polyfunctional aliphatic thiol compound (i.e., a difunctional or higher aliphatic thiol compound) is preferable, and from the viewpoint of adhesion of the formed pattern (particularly adhesion after exposure), a polyfunctional aliphatic thiol compound is more preferable.

[0162] In this specification, the term "polyfunctional aliphatic thiol compound" refers to an aliphatic compound having two or more thiol groups (also called "mercapto groups") in the molecule.

[0163] The molecular weight of the polyfunctional aliphatic thiol compound is preferably 100 or more, more preferably 100 to 1,500, and even more preferably 150 to 1,000.

[0164] The number of functional groups of the polyfunctional aliphatic thiol compound is preferably 2 to 10, more preferably 2 to 8, and even more preferably 2 to 6, from the viewpoint of adhesion of the formed pattern.

[0165] Examples of polyfunctional aliphatic thiol compounds include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, trimethylolpropane tris(3-mercaptopropionyloxy)ethyl]isocyanurate, ester), pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), ethylene glycol bisthiopropionate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,2-ethanedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethanethiol, meso-2,3-dimercaptosuccinic acid, and di(mercaptoethyl)ether. Among them, the polyfunctional aliphatic thiol compound is preferably at least one compound selected from the group consisting of trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.

[0166] Examples of monofunctional aliphatic thiol compounds include 1-octanethiol, 1-dodecanethiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.

[0167] The photosensitive composition layer may contain one kind of aliphatic thiol compound alone, or may contain two or more kinds of aliphatic thiol compounds.

[0168] When the photosensitive composition layer contains an aliphatic thiol compound, the content of the aliphatic thiol compound is preferably 5 mass% or more, more preferably 5 to 50 mass%, even more preferably 5 to 30 mass%, and particularly preferably 8 to 20 mass%, relative to the total mass of the photosensitive composition layer.

[0169] [Thermal crosslinkable compound] The photosensitive composition layer preferably contains a thermally crosslinkable compound from the viewpoints of the strength of the resulting cured film and the adhesion of the resulting uncured film. In this specification, a thermally crosslinkable compound having an ethylenically unsaturated group, which will be described later, is not regarded as an ethylenically unsaturated compound but as a thermally crosslinkable compound. The thermally crosslinkable compound is a compound different from the components contained in the above-mentioned photosensitive composition layer (such as the binder polymer, the polymerization initiator, and the polymerizable compound). Examples of the thermally crosslinkable compound include an epoxy compound, an oxetane compound, a methylol compound, and a blocked isocyanate compound. Among these, blocked isocyanate compounds are preferred from the viewpoints of the strength of the resulting cured film and the adhesiveness of the resulting uncured film. Since the blocked isocyanate compound reacts with a hydroxy group and a carboxy group, for example, when at least one of the binder polymer and the radically polymerizable compound having an ethylenically unsaturated group has at least one of a hydroxy group and a carboxy group, the hydrophilicity of the formed film tends to decrease and its function as a protective film tends to be enhanced. The blocked isocyanate compound refers to a compound having a structure in which the isocyanate group of an isocyanate is protected (so-called masked) with a blocking agent.

[0170] (First blocked isocyanate compound) The blocked isocyanate compound preferably contains a blocked isocyanate compound (hereinafter also referred to as a "first blocked isocyanate compound") having a blocked isocyanate equivalent (hereinafter also referred to as an "NCO value") of 4.5 mmol / g or more. This provides better bending resistance and also suppresses corrosion of the conductive layer.

[0171] The NCO value of the first blocked isocyanate compound is 4.5 mmol / g or more, and from the viewpoint of obtaining better effects of the present invention, it is more preferably 5.0 mmol / g or more, and even more preferably 5.3 mmol / g or more. The upper limit of the NCO value of the first blocked isocyanate compound is preferably 6.0 mmol / g or less, more preferably less than 5.8 mmol / g, and even more preferably 5.7 mmol / g or less, in terms of achieving better effects of the present invention. The NCO value of the blocked isocyanate compound in the present invention means the number of millimoles of blocked isocyanate groups contained per gram of the blocked isocyanate compound, and can be calculated from the following formula. Formula: NCO value of blocked isocyanate compound = 1000 x (number of blocked isocyanate groups contained in the molecule) / (molecular weight of blocked isocyanate compound)

[0172] The dissociation temperature of the first blocked isocyanate compound is preferably from 100 to 160°C, and more preferably from 110 to 150°C.

[0173] In this specification, the term "dissociation temperature of a blocked isocyanate compound" refers to the temperature of an endothermic peak accompanying the deprotection reaction of a blocked isocyanate compound, as measured by DSC (Differential Scanning Calorimetry) analysis using a differential scanning calorimeter. The differential scanning calorimeter is not particularly limited, and for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be suitably used.

[0174] Examples of blocking agents having a dissociation temperature of 100 to 160° C. include active methylene compounds (malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)) and oxime compounds (formaldoxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, cyclohexanone oxime, and other compounds having a structure represented by -C(=N-OH)- in the molecule). Among the above, oxime compounds are preferred as blocking agents having a dissociation temperature of 100 to 160° C. in terms of storage stability.

[0175] The first blocked isocyanate compound preferably has a ring structure in order to obtain better effects of the present invention. Examples of the ring structure include an aliphatic hydrocarbon ring, an aromatic hydrocarbon ring, and a heterocycle, and in order to obtain better effects of the present invention, an aliphatic hydrocarbon ring and an aromatic hydrocarbon ring are preferred, and an aliphatic hydrocarbon ring is more preferred. Specific examples of the aliphatic hydrocarbon ring include a cyclopentane ring and a cyclohexane ring, with the cyclohexane ring being preferred. Specific examples of the aromatic hydrocarbon ring include a benzene ring and a naphthalene ring, with the benzene ring being preferred. A specific example of the heterocyclic ring is an isocyanurate ring. When the first blocked isocyanate compound has a ring structure, from the viewpoint of better effects of the present invention, the number of rings is preferably 1 to 2, and more preferably 1. When the first blocked isocyanate compound contains a condensed ring, the number of rings constituting the condensed ring is counted, and for example, the number of rings in a naphthalene ring is counted as 2.

[0176] The number of blocked isocyanate groups in the first blocked isocyanate compound is preferably 2 to 5, more preferably 2 to 3, and even more preferably 2, in terms of excellent strength of the formed pattern and excellent effects of the present invention.

[0177] The first blocked isocyanate compound is preferably a blocked isocyanate compound represented by formula Q, since the effects of the present invention are more excellent. B 1 -A 1 -L 1 -A 2 -B 2 formula Q

[0178] In formula Q, B 1 and B. 2 each independently represents a blocked isocyanate group. The blocked isocyanate group is not particularly limited, but from the viewpoint of obtaining a more excellent effect of the present invention, a group in which an isocyanate group is blocked with an oxime compound is preferred, and a group in which an isocyanate group is blocked with methyl ethyl ketoxime (specifically, a group represented by *-NH-C(=O)-ON=C(CH3)-C2H5, where * is A 1 Or A 2 represents the bonding position with.) is more preferred. B 1 and B. 2 are preferably groups having the same structure.

[0179] In formula Q, A 1 and A 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms, and preferably an alkylene group having 1 to 10 carbon atoms. The alkylene group may be linear, branched or cyclic, and is preferably linear. The alkylene group has 1 to 10 carbon atoms, and preferably has 1 to 5 carbon atoms, more preferably 1 to 3 carbon atoms, and even more preferably 1 carbon atom, in terms of better effects of the present invention. A 1 and A 2 are preferably groups having the same structure.

[0180] In formula Q, L 1 represents a divalent linking group. Specific examples of the divalent linking group include divalent hydrocarbon groups. Specific examples of the divalent hydrocarbon group include a divalent saturated hydrocarbon group, a divalent aromatic hydrocarbon group, and a group formed by linking two or more of these groups. The divalent saturated hydrocarbon group may be linear, branched, or cyclic, and is preferably cyclic in view of the superior effect of the present invention. The number of carbon atoms in the divalent saturated hydrocarbon group is preferably 4 to 15, more preferably 5 to 10, and even more preferably 5 to 8, in view of the superior effect of the present invention. The divalent aromatic hydrocarbon group preferably has 5 to 20 carbon atoms, and an example of the group is a phenylene group. The divalent aromatic hydrocarbon group may have a substituent (for example, an alkyl group). Among these, the divalent linking group is preferably a linear, branched, or cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, a group in which a cyclic saturated hydrocarbon group having 5 to 10 carbon atoms is linked to a linear alkylene group having 1 to 3 carbon atoms, a divalent aromatic hydrocarbon group which may have a substituent, or a group in which a divalent aromatic hydrocarbon group is linked to a linear alkylene group having 1 to 3 carbon atoms, more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms or a phenylene group which may have a substituent, still more preferably a cyclohexylene group or a phenylene group which may have a substituent, and particularly preferably a cyclohexylene group.

[0181] The blocked isocyanate compound represented by formula Q is preferably a blocked isocyanate compound represented by formula QA, since the effects of the present invention are more excellent. B 1a -A 1a -L 1a -A 2a -B 2a QA

[0182] In the QA section, B 1a and B. 2a each independently represents a blocked isocyanate group. 1a and B. 2a A preferred embodiment of the formula Q is 1 and B. 2 is the same as:

[0183] In the QA, A 1a and A 2a each independently represents a divalent linking group. 1a and A 2a A preferred embodiment of the divalent linking group in formula Q is 1a and A 2a is the same as:

[0184] In the formula QA, L 1a represents a cyclic divalent saturated hydrocarbon group or a divalent aromatic hydrocarbon group. L 1a The cyclic divalent saturated hydrocarbon group in preferably has 5 to 10 carbon atoms, more preferably 5 to 8 carbon atoms, further preferably 5 or 6 carbon atoms, and particularly preferably 6 carbon atoms. L 1a A preferred embodiment of the divalent aromatic hydrocarbon group in the formula QA is 1 is the same as: Among them, L 1a is preferably a cyclic divalent saturated hydrocarbon group, more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, still more preferably a cyclic divalent saturated hydrocarbon group having 5 to 10 carbon atoms, particularly preferably a cyclic divalent saturated hydrocarbon group having 5 to 6 carbon atoms, and most preferably a cyclohexylene group.

[0185] Specific examples of the first blocked isocyanate compound are shown below, but the first blocked isocyanate compound is not limited thereto.

[0186] [ka]

[0187] The photosensitive composition layer may contain one kind of first blocked isocyanate compound alone, or may contain two or more kinds of first blocked isocyanate compounds.

[0188] The content of the first blocked isocyanate compound is preferably from 0.50 to 25.00% by mass, more preferably from 1.00 to 20.00% by mass, and further preferably from 1.50 to 5.00% by mass, based on the total mass of the photosensitive composition layer.

[0189] The first blocked isocyanate compound is, for example, a compound having an isocyanate group (for example, B 1 and B. 2 is an isocyanate group) with the above blocking agent.

[0190] (Second blocked isocyanate compound) The blocked isocyanate compound preferably contains a blocked isocyanate compound having an NCO value of less than 4.5 mmol / g (hereinafter also referred to as a "second blocked isocyanate compound"), which can suppress the generation of development residues after the photosensitive composition layer is subjected to pattern exposure and development.

[0191] The NCO value of the second blocked isocyanate compound is less than 4.5 mmol / g, preferably 2.0 mmol / g or more and less than 4.5 mmol / g, and more preferably 2.5 to 4.0 mmol / g.

[0192] The dissociation temperature of the second blocked isocyanate compound is preferably from 100 to 160°C, and more preferably from 110 to 150°C. Specific examples of the blocking agent having a dissociation temperature of 100 to 160° C. are as described above.

[0193] The second blocked isocyanate compound preferably has an isocyanurate structure from the viewpoint of improving the brittleness of the film or improving the adhesion to the transfer target, etc. A blocked isocyanurate compound having an isocyanurate structure can be obtained, for example, by protecting hexamethylene diisocyanate through isocyanuration.

[0194] As the blocked isocyanurate compound having an isocyanurate structure, a compound having an oxime structure in which an oxime compound is used as a blocking agent is preferred, since it is easier to set the dissociation temperature in a preferred range and to reduce development residues than a compound not having an oxime structure.

[0195] The second blocked isocyanate compound may have a polymerizable group from the viewpoint of the strength of the pattern to be formed. The polymerizable group is preferably a radically polymerizable group. Examples of the polymerizable group include ethylenically unsaturated groups such as (meth)acryloxy groups, (meth)acrylamide groups, and styryl groups, as well as groups having an epoxy group such as glycidyl groups. Among the above, the polymerizable group is preferably an ethylenically unsaturated group, and more preferably a (meth)acryloxy group, from the viewpoints of the surface condition of the resulting pattern, development speed, and reactivity.

[0196] Specific examples of the second blocked isocyanate compound are shown below, but the second blocked isocyanate compound is not limited thereto.

[0197] [ka]

[0198] The second blocked isocyanate compound may be a commercially available product. Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) AOI-BP, Karenz (registered trademark) MOI-BP (all manufactured by Showa Denko K.K.), and the blocked Duranate series (e.g., Duranate (registered trademark) TPA-B80E, manufactured by Asahi Kasei Chemicals Corporation).

[0199] The photosensitive composition layer may contain one type of second blocked isocyanate compound alone, or may contain two or more types of second blocked isocyanate compounds.

[0200] When the photosensitive composition layer contains the second blocked isocyanate compound, the content of the second blocked isocyanate compound is preferably 1.00 to 25.00 mass%, more preferably 1.00 to 20.0 mass%, and even more preferably 10.00 to 15.00 mass%, relative to the total mass of the photosensitive composition layer, from the viewpoint of further reducing the generation of development residues.

[0201] When the photosensitive composition layer contains the first blocked isocyanate compound and the second blocked isocyanate compound, the mass ratio of the content of the first blocked isocyanate compound to the content of the second blocked isocyanate compound (first blocked isocyanate compound / second blocked isocyanate compound) is preferably 0.10 to 9.00, more preferably 0.18 to 2.35, and even more preferably 0.18 to 1.00, from the viewpoints of bending resistance and reduced moisture permeability.

[0202] The thermally crosslinkable compound may be used alone or in combination of two or more kinds. When the photosensitive composition layer contains a thermally crosslinkable compound, the content of the thermally crosslinkable compound is preferably 1.00 to 50.00 mass %, more preferably 10.00 to 30.00 mass %, and even more preferably 15.00 to 20.00 mass %, relative to the total mass of the photosensitive composition layer.

[0203] [Surfactants] The photosensitive composition layer may contain a surfactant. Examples of the surfactant include those described in paragraph

[0017] of Japanese Patent No. 4,502,784 and paragraphs

[0060] to

[0071] of JP-A-2009-237362, the contents of which are incorporated herein by reference. Examples of the surfactant include fluorine-based surfactants, silicone-based surfactants, and hydrocarbon-based surfactants, of which fluorine-based surfactants and silicone-based surfactants are preferred, and fluorine-based surfactants are more preferred. Furthermore, the surfactant is preferably a nonionic surfactant.

[0204] Commercially available fluorine-based surfactants include, for example, Megafac F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP, and MFS-3. 30, EXP.MFS-578, EXP.MFS-578-2, EXP.MFS-579, EXP.MFS-586, EXP.MFS-587, EXP.MFS-628, EXP.MFS-631, EXP.MFS-603, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, and DS-21 (all manufactured by DIC); Fluorad FC430, FC431, FC171 (all manufactured by Sumitomo 3M); Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, and KH-40 (all manufactured by AGC); PolyFox PF636, PF656, PF6320, PF6520, and PF7002 (all manufactured by OMNOVA); Futergent Examples include 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, and 681 (all manufactured by NEOS Corporation), and U-120E (Unichem Corporation). In addition, the fluorosurfactant may be an acrylic compound that has a molecular structure with a functional group containing a fluorine atom, and when heat is applied, the functional group containing the fluorine atom is broken and the fluorine atom is volatilized. Examples of such fluorosurfactants include the Megafac DS series manufactured by DIC Corporation (The Chemical Daily, February 22, 2016; Nikkei Business Daily, February 23, 2016, for example, Megafac DS-21).

[0205] As the fluorine-based surfactant, it is also preferable to use a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound.

[0206] The fluorine-based surfactant may be a block polymer. The fluorine-based surfactant may be a fluorine-containing polymer compound that contains a repeating unit derived from a (meth)acrylate compound having a fluorine atom and a repeating unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy groups, propyleneoxy groups).

[0207] The fluorine-based surfactant may be a fluorine-containing polymer having an ethylenically unsaturated bond-containing group in the side chain, such as Megafac RS-101, RS-102, RS-718K, and RS-72-K (all manufactured by DIC Corporation).

[0208] From the viewpoint of improving environmental compatibility, it is preferable that the fluorosurfactant be a surfactant derived from an alternative material to compounds having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS).

[0209] Examples of silicone surfactants include linear polymers formed from siloxane bonds, and modified siloxane polymers in which organic groups have been introduced into the side chains or ends. Commercially available silicone surfactants include EXP.S-309-2, EXP.S-315, EXP.S-503-2, EXP.S-505-2 (all manufactured by DIC Corporation), DOWSIL 8032 ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all manufactured by Dow Corning Toray Co., Ltd.); X-22-4952, X-22-4272, X- 22-6266, KF-351A, K354L, KF-355A, KF-945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-600 4, KP-341, KF-6001, KF-6002, KP-101KP-103, KP-104, KP-105, KP-106, KP-109, KP-109, KP-112, KP-12 0, KP-121, KP-124, KP-125, KP-301, KP-306, KP-310, KP-322, KP-323, KP-327, KP-341, KP-368, KP-369, KP-611, KP-620, KP-621, KP-626, and KP-652 (all manufactured by Shin-Etsu Silicones); F-4440, TSF-4300, TSF-4445, and TSF- 4460, TSF-4452 (all manufactured by Momentive Performance Materials); BYK307, BYK323, BYK330, BYK313, BYK315N, BYK331, BYK333, BYK345, BYK347, BYK348, BYK349, BYK370, BYK377, BYK378, and BYK323 (all manufactured by BYK-Chemie).

[0210] Examples of hydrocarbon surfactants include glycerol, trimethylolpropane, trimethylolethane, and their ethoxylates and propoxylates (e.g., glycerol propoxylate, glycerol ethoxylate, etc.); polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, and sorbitan fatty acid esters. Commercially available hydrocarbon surfactants include Pluronic (registered trademark) L10, L31, L61, L62, 10R5, 17R2, and 25R2 (all manufactured by BASF); Tetronic 304, 701, 704, 901, 904, and 150R1 (all manufactured by BASF); Solsperse 20000 (all manufactured by Lubrizol Japan); NCW-101, NCW-1001, and NCW-1002 (all manufactured by Fujifilm Wako Pure Chemical Industries); Paionin D-6112, D-6112-W, and D-6315 (all manufactured by Takemoto Oil Co., Ltd.), Olfin E1010, Surfynol 104, 400, and 440 (all manufactured by Nissin Chemical Industry Co., Ltd.).

[0211] The surfactant may be used alone or in combination of two or more kinds. When the photosensitive composition layer contains a surfactant, the content of the surfactant is preferably 0.01 to 3.0 mass %, more preferably 0.05 to 1.0 mass %, and even more preferably 0.10 to 0.80 mass %, relative to the total mass of the photosensitive composition layer.

[0212] [Phosphate ester compounds] The photosensitive composition layer may contain a phosphate ester compound. The phosphate ester compound is not particularly limited as long as at least one of the three hydrogen atoms in phosphoric acid (O=P(OH)3) is substituted with an organic group, and examples thereof include the Phosmer series (Phosmer-M, Phosmer-CL, Phosmer-PE, Phosmer-MH, Phosmer-PP) manufactured by Unichemical Co., Ltd., the KAYAMER series (KAYAMER PM-21, KAYAMER PM-2) manufactured by Nippon Kayaku Co., Ltd., and the Light Ester series (Light Ester P-2M (product name)) manufactured by Kyoeisha Chemical Co., Ltd.

[0213] The phosphate ester compounds may be used alone or in combination of two or more kinds. The content of the phosphate ester compound is not particularly limited, but is preferably from 0.05 to 3.0% by mass, more preferably from 0.1 to 2.0% by mass, and even more preferably from 0.2 to 1.0% by mass, based on the total mass of the photosensitive composition layer. When the photosensitive composition layer contains a phosphoric acid ester compound, the content of the phosphoric acid ester compound is not particularly limited, but from the viewpoint of further improving the adhesion to the transfer target, it is preferably 10 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by mass of the binder polymer and the polymerizable compound in total. In addition, the upper limit of the content is not particularly limited, but it is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more.

[0214] [Polymerization inhibitor] The photosensitive composition layer may contain a polymerization inhibitor. The polymerization inhibitor means a compound having a function of delaying or inhibiting a polymerization reaction. As the polymerization inhibitor, for example, a known compound used as a polymerization inhibitor can be used.

[0215] Examples of the polymerization inhibitor include phenothiazine compounds such as phenothiazine, bis-(1-dimethylbenzyl)phenothiazine, and 3,7-dioctylphenothiazine; bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][ethylenebis(oxyethylene)]2,4-bis[(laurylthio)methyl]-o-cresol, 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl), 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethylbenzyl), 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, and pentaerythritol tetrakis 3-(3,5-di-te nitroso compounds or salts thereof, such as 4-nitrosophenol, N-nitrosodiphenylamine, N-nitrosocyclohexylhydroxylamine, and N-nitrosophenylhydroxylamine; quinone compounds, such as methylhydroquinone, t-butylhydroquinone, 2,5-di-t-butylhydroquinone, and 4-benzoquinone; phenol compounds, such as 4-methoxyphenol, 4-methoxy-1-naphthol, and t-butylcatechol; and metal salt compounds, such as copper dibutyldithiocarbamate, copper diethyldithiocarbamate, manganese diethyldithiocarbamate, and manganese diphenyldithiocarbamate. Among them, the polymerization inhibitor is preferably at least one selected from the group consisting of a phenothiazine compound, a nitroso compound or a salt thereof, and a hindered phenol compound, and more preferably phenothiazine, bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionic acid][ethylene bis(oxyethylene)]2,4-bis[(laurylthio)methyl]-o-cresol, 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl), and N-nitrosophenylhydroxylamine aluminum salt.

[0216] The polymerization inhibitor may be used alone or in combination of two or more kinds. When the photosensitive composition layer contains a polymerization inhibitor, the content of the polymerization inhibitor is preferably 0.01 to 10.0 mass %, more preferably 0.05 to 5.00 mass %, and further preferably 0.10 to 3.00 mass %, based on the total mass of the photosensitive composition layer.

[0217] [Hydrogen donor compounds] The photosensitive composition layer may contain a hydrogen donor compound. The hydrogen donor compound has the effect of further improving the sensitivity of the photopolymerization initiator to actinic rays and suppressing the polymerization inhibition of the polymerizable compound caused by oxygen.

[0218] Examples of hydrogen donor compounds include amines and amino acid compounds.

[0219] Examples of amines include compounds described in MR Sander et al., Journal of Polymer Society, Vol. 10, p. 3173 (1972), JP-B-020189 / 1969, JP-A-51-082102, JP-A-52-134692, JP-A-59-138205, JP-A-60-084305, JP-A-62-018537, JP-A-64-033104, and Research Disclosure No. 33825. More specifically, 4,4'-bis(diethylamino)benzophenone, tris(4-dimethylaminophenyl)methane (also known as leuco crystal violet), triethanolamine, p-dimethylaminobenzoic acid ethyl ester, p-formyldimethylaniline, and p-methylthiodimethylaniline. Among these, in terms of obtaining superior effects of the present invention, the amine is preferably at least one selected from the group consisting of 4,4'-bis(diethylamino)benzophenone and tris(4-dimethylaminophenyl)methane.

[0220] Examples of the amino acid compounds include N-phenylglycine, N-methyl-N-phenylglycine, and N-ethyl-N-phenylglycine. Among these, N-phenylglycine is preferred as the amino acid compound in that the effects of the present invention are more excellent.

[0221] Further, examples of hydrogen donor compounds include organometallic compounds (such as tributyltin acetate) described in JP-B-48-042965, hydrogen donors described in JP-B-55-034414, and sulfur compounds (such as trithiane) described in JP-A-6-308727.

[0222] The hydrogen donor compounds may be used alone or in combination of two or more kinds. When the photosensitive composition layer contains a hydrogen donor compound, the content of the hydrogen donor compound is preferably 0.01 to 10.00 mass%, more preferably 0.03 to 8.00 mass%, and even more preferably 0.05 to 5.00 mass%, relative to the total mass of the photosensitive composition layer, from the viewpoint of improving the curing rate through a balance between the polymerization growth rate and chain transfer.

[0223] [Residual monomer] The photosensitive composition layer may contain residual monomers of each structural unit of the binder polymer described above. From the viewpoints of patterning property and reliability, the content of the residual monomer is preferably 5,000 ppm by mass or less, more preferably 2,000 ppm by mass or less, and even more preferably 500 ppm by mass or less, based on the total mass of the binder polymer. Although there is no particular lower limit, it is preferably 1 ppm by mass or more, and more preferably 10 ppm by mass or more, based on the total mass of the binder polymer. From the viewpoints of patterning property and reliability, the residual monomer of each structural unit of the binder polymer is preferably 3,000 mass ppm or less, more preferably 600 mass ppm or less, and even more preferably 100 mass ppm or less, based on the total mass of the photosensitive composition layer. Although there is no particular lower limit, it is preferably 0.1 mass ppm or more, and more preferably 1 mass ppm or more, based on the total mass of the photosensitive composition layer.

[0224] The amount of residual monomers in the synthesis of a binder polymer by a polymer reaction is also preferably within the above range. For example, when the binder polymer is synthesized by reacting glycidyl acrylate with a carboxylic acid side chain, the content of glycidyl acrylate is preferably within the above range. The amount of the residual monomer can be measured by a known method such as liquid chromatography or gas chromatography.

[0225] [Other ingredients] The photosensitive composition layer may contain components other than those described above (hereinafter also referred to as "other components"). Examples of the other components include colorants, antioxidants, and particles (e.g., metal oxide particles). Examples of the other components include other additives described in paragraphs

[0058] to

[0071] of JP-A-2000-310706.

[0226] -particle- The particles are preferably metal oxide particles. The metals in the metal oxide particles include metalloids such as B, Si, Ge, As, Sb, and Te. The average primary particle size of the particles is, for example, preferably from 1 to 200 nm, more preferably from 3 to 80 nm, from the viewpoint of the transparency of the cured film. The average primary particle size of particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and taking the arithmetic mean of the measurement results. If the particle shape is not spherical, the longest side is used as the particle size.

[0227] When the photosensitive composition layer contains particles, it may contain only one type of particles having different metal species, sizes, etc., or may contain two or more types of particles. The photosensitive composition layer does not contain particles, or if the photosensitive composition layer contains particles, the particle content is preferably more than 0 mass% and 35 mass% or less, relative to the total mass of the photosensitive composition layer; more preferably, the photosensitive composition layer does not contain particles or the particle content is more than 0 mass% and 10 mass% or less, relative to the total mass of the photosensitive composition layer; even more preferably, the photosensitive composition layer does not contain particles or the particle content is more than 0 mass% and 5 mass% or less, relative to the total mass of the photosensitive composition layer; even more preferably, the photosensitive composition layer does not contain particles or the particle content is more than 0 mass% and 1 mass% or less, relative to the total mass of the photosensitive composition layer; and particularly preferably, the photosensitive composition layer does not contain particles.

[0228] -Coloring agent- The photosensitive composition layer may contain a small amount of a colorant (pigment, dye, etc.). However, from the standpoint of transparency, for example, it is preferable that the photosensitive composition layer contains substantially no colorant. When the photosensitive composition layer contains a colorant, the content of the colorant is preferably less than 1% by mass, more preferably less than 0.1% by mass, based on the total mass of the photosensitive composition layer. There is no particular lower limit, and 0% by mass is preferred.

[0229] -Antioxidants- Examples of antioxidants include 3-pyrazolidones such as 1-phenyl-3-pyrazolidone (also known as phenidone), 1-phenyl-4,4-dimethyl-3-pyrazolidone, and 1-phenyl-4-methyl-4-hydroxymethyl-3-pyrazolidone; polyhydroxybenzenes such as hydroquinone, catechol, pyrogallol, methylhydroquinone, and chlorohydroquinone; paramethylaminophenol, paraaminophenol, parahydroxyphenylglycine, and paraphenylenediamine. Among these, 3-pyrazolidones are preferred as the antioxidant, and 1-phenyl-3-pyrazolidone is more preferred, in terms of the superior effect of the present invention.

[0230] When the photosensitive composition layer contains an antioxidant, the content of the antioxidant is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more, based on the total mass of the photosensitive composition layer. The upper limit is not particularly limited, but is preferably 1% by mass or less, based on the total mass of the photosensitive composition layer.

[0231] [impurities] The photosensitive composition layer may contain impurities. Examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and ions thereof. Among these, halide ions, sodium ions, and potassium ions are likely to be mixed in as impurities, so it is preferable to set the contents to the following amounts.

[0232] The content of impurities in the photosensitive composition layer is preferably 80 mass ppm or less, more preferably 10 mass ppm or less, and even more preferably 2 mass ppm or less, based on the total mass of the photosensitive composition layer. The lower limit is not particularly limited, and is preferably 1 mass ppb or more, and more preferably 0.1 mass ppm or more, based on the total mass of the photosensitive composition layer.

[0233] Methods for controlling the amount of impurities within the above range include selecting raw materials for the photosensitive composition layer that have a low content of impurities, preventing impurities from being mixed in during the formation of the photosensitive composition layer, and removing them by washing. By such methods, the amount of impurities can be controlled within the above range.

[0234] The amount of impurities can be quantified by known methods such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, and ion chromatography.

[0235] The content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, and hexane in the photosensitive composition layer is preferably low. These compounds are preferably 100 mass ppm or less, more preferably 20 mass ppm or less, and even more preferably 4 mass ppm or less, based on the total mass of the photosensitive composition layer. There is no particular lower limit, and the content is preferably 10 mass ppb or more, more preferably 100 mass ppb or more, based on the total mass of the photosensitive composition layer. The content of these compounds can be suppressed in the same manner as the above-mentioned metal impurities. They can also be quantified by known measurement methods.

[0236] The content of water in the photosensitive composition layer is preferably 0.01 to 1.0 mass %, and more preferably 0.05 to 0.5 mass %, based on the total mass of the photosensitive composition layer, from the viewpoint of improving reliability and lamination properties.

[0237] [Refractive index adjustment layer] The transfer film may have a refractive index adjusting layer disposed on the photosensitive composition layer. The transfer film preferably has a temporary support, a photosensitive composition layer, and a refractive index adjusting layer in this order. When the transfer film further has a protective film described below, it preferably has a temporary support, a photosensitive composition layer, a refractive index adjusting layer, and a protective film described below in this order.

[0238] The refractive index adjusting layer may be a known refractive index adjusting layer. Examples of materials contained in the refractive index adjusting layer include a binder and particles.

[0239] Examples of the binder include a binder polymer contained in the photosensitive composition layer and a polymer containing a structural unit having a carboxylic acid anhydride structure.

[0240] Examples of the particles include zirconium oxide particles (ZrO2 particles), niobium oxide particles (Nb2O5 particles), titanium oxide particles (TiO2 particles), and silicon dioxide particles (SiO2 particles).

[0241] The refractive index adjusting layer preferably contains a metal oxidation inhibitor. By including a metal oxidation inhibitor in the refractive index matching layer, oxidation of the metal in contact with the refractive index matching layer can be suppressed. The metal oxidation inhibitor is preferably, for example, a compound having an aromatic ring containing a nitrogen atom in the molecule, and examples of the metal oxidation inhibitor include imidazole, benzimidazole, tetrazole, mercaptothiadiazole, and benzotriazole.

[0242] The refractive index of the refractive index adjusting layer is preferably 1.60 or more, more preferably 1.63 or more. There is no particular upper limit, but the refractive index is preferably 2.10 or less, more preferably 1.85 or less.

[0243] The thickness of the refractive index adjusting layer is preferably 500 nm or less, more preferably 110 nm or less, and even more preferably 100 nm or less. There is no upper limit, but the thickness is preferably 20 nm or more, and more preferably 50 nm or more. The thickness of the refractive index adjusting layer is calculated as the average value of any five points measured by cross-sectional observation using a scanning electron microscope (SEM).

[0244] [Other layers] The transfer film may have layers other than the above-mentioned temporary support, photosensitive composition layer, and refractive index adjusting layer. The other layers include, for example, a protective film and an antistatic layer.

[0245] The transfer film may have a protective film for protecting the photosensitive composition layer on the surface opposite to the temporary support. The protective film is preferably a resin film, and a resin film having heat resistance and solvent resistance can be used. Examples of the protective film include polyolefin films such as polypropylene films and polyethylene films. Alternatively, a resin film made of the same material as the above-mentioned temporary support may be used as the protective film.

[0246] The thickness of the protective film is preferably 1 to 100 μm, more preferably 5 to 50 μm, further preferably 5 to 40 μm, and particularly preferably 15 to 30 μm. The thickness of the protective film is preferably 1 μm or more in terms of excellent mechanical strength, and is preferably 100 μm or less in terms of relatively low cost.

[0247] The transfer film may include an antistatic layer. By having an antistatic layer in a transfer film, the generation of static electricity when peeling off a film or the like placed on the antistatic layer can be suppressed, and the generation of static electricity due to rubbing with equipment or other films, etc. can also be suppressed, thereby preventing malfunctions in electronic devices, for example. The antistatic layer is preferably disposed between the temporary support and the photosensitive composition layer.

[0248] The antistatic layer is a layer having antistatic properties and contains at least an antistatic agent. The antistatic agent is not particularly limited, and any known antistatic agent can be used.

[0249] [Method of manufacturing transfer film] The method for producing the transfer film of the present invention is not particularly limited, and any known method can be used. Among these, the method of coating a photosensitive composition on a temporary support, optionally followed by drying treatment to form a photosensitive composition layer is preferred from the viewpoint of excellent productivity. The above method will now be described in detail.

[0250] Examples of methods for applying the photosensitive composition include printing, spraying, roll coating, bar coating, curtain coating, spin coating, and die coating (that is, slit coating).

[0251] Examples of the drying method include natural drying, heat drying, and reduced pressure drying. The above-mentioned methods can be applied alone or in combination. In this specification, "drying" means removing at least a portion of the solvent contained in the photosensitive composition.

[0252] When the transfer film has a refractive index adjusting layer on a photosensitive composition layer, for example, a composition for forming a refractive index adjusting layer can be applied onto the photosensitive composition layer and then dried as necessary to form the refractive index adjusting layer.

[0253] When the transfer film has a protective film, the transfer film can be produced by laminating the protective film to the photosensitive composition layer. The method for attaching the protective film to the photosensitive composition layer is not particularly limited, and any known method can be used. Examples of a device for laminating the protective film to the photosensitive composition layer include known laminators such as a vacuum laminator and an autocut laminator. The laminator is preferably equipped with any heatable roller, such as a rubber roller, and is capable of applying pressure and heat.

[0254] [Method for producing laminate] By using the above-mentioned transfer film, the photosensitive composition layer can be transferred to a receiving material. Among them, the method includes a lamination step of contacting a surface of the transfer film opposite to the temporary support with a transferee, thereby obtaining a transferee with a photosensitive composition layer having the transferee, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A developing step of developing the exposed photosensitive composition layer to form a pattern, Furthermore, the method for producing a laminate preferably includes a peeling step of peeling the temporary support from the transfer-receiving body with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step. In the laminate manufacturing method of the present invention, by virtue of such a configuration, even when a substrate having steps is used as the receiving body, the occurrence of wrinkles during lamination onto the substrate having steps can be suppressed, and in particular, the occurrence of wrinkles during lamination onto the substrate having steps can be suppressed in the region along the steps (44 in Figure 1). The steps of the above process will be described in detail below.

[0255] <Lamination process> The lamination process is a process in which the surface of the transfer film opposite the temporary support is brought into contact with and laminated to a transferee, thereby obtaining a transferee with a photosensitive composition layer having the transferee, the photosensitive composition layer, and the temporary support in that order. In addition, when a substrate having steps is used as the object to be transferred, the process is preferably such that the photosensitive composition layer on the temporary support of the transfer film is brought into contact with the substrate having steps, and the layers are laminated so as to continuously cover the upper and lower parts of the steps that constitute the steps, thereby obtaining a substrate with a photosensitive composition layer having the substrate, the photosensitive composition layer, and the temporary support in that order. In addition, the surface of the transfer film opposite to the temporary support is preferably a refractive index adjusting layer when the transfer film has a refractive index adjusting layer, and is preferably a photosensitive composition layer when the transfer film does not have a refractive index adjusting layer. In other words, the lamination step is preferably performed by contacting the refractive index adjusting layer of the transfer film with the transfer target and laminating it, or by contacting the photosensitive composition layer of the transfer film with the transfer target and laminating it.

[0256] The exposed photosensitive composition layer on the temporary support of the transfer film is brought into contact with an object to be transferred and laminated together, so that the photosensitive composition layer and the temporary support are disposed on the object to be transferred. In the lamination, the transfer-receiving material and the surface of the photosensitive composition layer are pressed together so as to come into contact with each other. The method of pressure bonding is not particularly limited, and known transfer methods and lamination methods can be used. Among them, it is preferable to perform the pressure bonding by superposing the surface of the photosensitive composition layer on a substrate having a step, and applying pressure and heat with a roll or the like. For lamination, a known laminator such as a vacuum laminator or an autocut laminator can be used.

[0257] The type of the transfer substrate is not particularly limited, and examples thereof include a glass substrate, a resin substrate, and a metal substrate, and may also be a laminate of these. The object to be transferred may be, for example, a substrate having a step.

[0258] The method for preparing the substrate having a step is not particularly limited. The substrate included in the substrate having a step is preferably, for example, a transparent substrate.

[0259] In order to improve the adhesion of each layer by lamination in the above-mentioned attachment step, the contact surface of the substrate (particularly when the substrate is a transparent substrate (front panel)) having a step may be subjected to a surface treatment in advance. The surface treatment is not particularly limited, and any known method capable of improving adhesion can be used. Among them, it is preferable to carry out the surface treatment using a silane compound (preferably a silane coupling agent). As the silane coupling agent, one having a functional group that interacts with the photosensitive composition layer is preferable. Specifically, a silane coupling liquid (0.3 mass% aqueous solution of N-β(aminoethyl)γ-aminopropyltrimethoxysilane, product name: KBM603, manufactured by Shin-Etsu Chemical Co., Ltd.) is sprayed by shower for 20 seconds, washed by shower with pure water, and reacted by heating. A heating tank may be used, or a substrate preheating of a laminator may be used. When the lower portion of the step constituting the step is a member other than the substrate, a step of providing the other member on the substrate may be included.

[0260] The thickness of the steps constituting the above-mentioned step difference is preferably 100 nm or more, more preferably 100 to 500 nm, and even more preferably 100 to 300 nm. The substrate 43 having a step shown in Fig. 1 has a step 41 constituting a step on the substrate 1A. The thickness of the step 41 constituting the step corresponds to the height (distance) between the upper part 41a of the step constituting the step and the lower part 41b of the step constituting the step. In Fig. 1, the thickness of the step 41 constituting the step is described as 100 nm, but the substrate having a step used in the manufacturing method of the laminate of the present invention is not limited to this embodiment. In addition, in FIG. 1, the size of the step 41 when viewed from above the substrate 1A is described as 2 cm in length and 5 cm in width, but this is merely an example and is not limited to this. Furthermore, the upper portion of the step that constitutes the step may be a flat surface or a curved surface. In addition, the shape of the steps that make up the step may be an inclined structure (so-called tapered shape) in which the sides of the steps that make up the step are narrower at the top than at the bottom, or the top and bottom of the step may have the same structure. The angle between the side of the step constituting the step (41b in FIG. 1) and the substrate (1A in FIG. 1) is not particularly limited, and is preferably 5 to 90°.

[0261] In addition, the manufacturing method of the laminate of the present invention preferably includes a step-up step of stacking the above-mentioned photosensitive composition layer in this order from the lower part of the step (41c in FIG. 1) to the upper part of the step (41a in FIG. 1) constituting the above-mentioned step, and a step-down step of stacking the above-mentioned photosensitive composition layer in this order from the upper part of the step (41a in FIG. 1) to the lower part of the step (41c in FIG. 1). Even when the step-up step and the step-down step are included in this way, according to the manufacturing method of the laminate of the present invention, it is possible to suppress the inclusion of wrinkles during lamination on a substrate having a step, particularly in the region 44 along the step in FIG. 1. The step-up step is performed when the photosensitive composition layer climbs up the step at the step on the side closer to the lamination direction 42 in FIG. 1. The step-down step is performed when the photosensitive composition layer goes over the step at the step on the side farther from the lamination direction 42 in FIG. 1.

[0262] The steps constituting the above-mentioned step difference may include a conductive element, such as a conductive layer described below.

[0263] The object to be transferred may be a substrate having a conductive layer. The substrate having a conductive layer has a conductive layer on a substrate, and may have an optional layer formed thereon, i.e., the substrate having a conductive layer is a conductive substrate having at least a substrate and a conductive layer disposed on the substrate. Examples of the substrate include a resin substrate, a glass substrate, and a semiconductor substrate. A preferred embodiment of the substrate is described, for example, in paragraph

[0140] of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.

[0264] From the viewpoints of electrical conductivity and fine line formability, the conductive layer is preferably at least one layer selected from the group consisting of a metal layer, a conductive metal oxide layer, a graphene layer, a carbon nanotube layer, and a conductive polymer layer. Furthermore, only one conductive layer may be disposed on the substrate, or two or more conductive layers may be disposed on the substrate. When two or more conductive layers are disposed, it is preferable that the conductive layers are made of different materials. A preferred embodiment of the conductive layer is described, for example, in paragraph

[0141] of International Publication No. 2018 / 155193, the contents of which are incorporated herein by reference.

[0265] The substrate having a conductive layer is preferably a substrate having at least one of a transparent electrode and a routed wiring. Such a substrate can be suitably used as a substrate for a touch panel. The transparent electrode can function favorably as a touch panel electrode. The transparent electrode is preferably composed of a metal oxide film such as ITO (indium tin oxide) or IZO (indium zinc oxide), a metal mesh, or a metal thin wire such as silver nanowire. Examples of the thin metal wires include thin wires of silver, copper, etc. Among them, conductive silver materials such as silver mesh and silver nanowires are preferred.

[0266] The material of the lead wiring is preferably a metal. Examples of metals that are the material of the wiring include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, and manganese, and alloys of two or more of these metal elements. Among these, the material of the wiring is preferably copper, molybdenum, aluminum, or titanium, and more preferably copper.

[0267] <Exposure process> The exposure step is a step of pattern-exposing the photosensitive composition layer. Here, the term "pattern exposure" refers to a form of exposure in a pattern, that is, exposure in a form in which exposed areas and non-exposed areas exist. The detailed arrangement and specific size of the pattern in the pattern exposure are not particularly limited. The pattern formed by the developing step described below preferably includes a thin line having a width of 20 μm or less, more preferably includes a thin line having a width of 10 μm or less.

[0268] The light source for the pattern exposure can be appropriately selected and used as long as it can irradiate light in a wavelength range (e.g., 365 nm or 405 nm) that can at least cure the photosensitive composition layer. Among them, the dominant wavelength of the exposure light for the pattern exposure is preferably 365 nm. The dominant wavelength is the wavelength with the highest intensity.

[0269] Examples of light sources include various lasers, light-emitting diodes (LEDs), ultra-high pressure mercury lamps, high pressure mercury lamps, and metal halide lamps. The exposure dose is 5 to 200 mJ / cm 2 is preferable, and 10 to 200 mJ / cm 2 is more preferred.

[0270] Preferred embodiments of the light source, exposure dose, and exposure method used for exposure are described, for example, in paragraphs

[0146] to

[0147] of WO 2018 / 155193, the contents of which are incorporated herein by reference.

[0271] <Peeling process> The peeling step is a step of peeling off the temporary support from the transfer-receiving material having the photosensitive composition layer thereon between the laminating step and the exposure step, or between the exposure step and the development step described below. The peeling method is not particularly limited, and a mechanism similar to the cover film peeling mechanism described in paragraphs

[0161] to

[0162] of JP2010-072589A can be used.

[0272] <Developing process> The development step is a step of developing the exposed photosensitive composition layer to form a pattern. The photosensitive composition layer can be developed using a developer. The developer is preferably an alkaline aqueous solution. Examples of alkaline compounds that can be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide).

[0273] Examples of the development method include paddle development, shower development, spin development, and dip development.

[0274] In this specification, examples of the developer that can be suitably used include the developer described in paragraph

[0194] of WO 2015 / 093271. An example of a development method that can be suitably used is the development method described in paragraph

[0195] of WO 2015 / 093271.

[0275] The detailed arrangement and the specific size of the pattern to be formed are not particularly limited, but a pattern that can obtain the conductive thin wire described later is formed. The interval between the patterns is preferably 8 μm or less, more preferably 6 μm or less. The lower limit is not particularly limited, but is often 2 μm or more.

[0276] The pattern (protective film for the photosensitive composition layer) formed by the above procedure is preferably achromatic. * a * b * In the color system, pattern a * The value is preferably -1.0 to 1.0, and the b * The value is preferably in the range of -1.0 to 1.0.

[0277] <Post-exposure process and post-bake process> The method for producing the laminate may include a step of exposing the pattern obtained by the development step (a post-exposure step) and / or a step of heating the pattern (a post-bake step). When both a post-exposure step and a post-bake step are included, it is preferable to carry out the post-bake step after the post-exposure step.

[0278] [Method of manufacturing circuit wiring] The transfer film can also be used in a method for producing circuit wiring. The method for producing the circuit wiring is not particularly limited, and may be any known production method. Among them, the manufacturing method of circuit wiring is as follows: a lamination step of laminating the photosensitive composition layer on the temporary support of the transfer film to a transferee including a conductive layer to obtain a transferee having a photosensitive composition layer, the transferee having a transferee, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; a developing step of developing the exposed photosensitive composition layer to form a pattern; an etching step for etching the conductive layer in areas where no pattern is disposed; Furthermore, the method for producing a laminate preferably includes a peeling step of peeling the temporary support from the transfer-receiving body having the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.

[0279] In the method for producing circuit wiring, the laminating step, the exposure step, the development step, and the peeling step are the same as the respective steps in the above-mentioned <method for producing laminate>, and the preferred ranges are also the same.

[0280] <Etching process> The etching step is a step (etching step) of etching the conductive layer in the area where the pattern obtained in the development step is not arranged. That is, the etching step involves performing an etching treatment on the conductive layer using the pattern formed from the photosensitive composition layer as an etching resist.

[0281] As the etching step, a known method can be applied, and examples thereof include the method described in paragraphs

[0209] to

[0210] of JP2017-120435A, the method described in paragraphs

[0048] to

[0054] of JP2010-152155A, a wet etching method in which the substrate is immersed in an etching solution, and a dry etching method using plasma etching.

[0282] The etching solution used in the wet etching may be an acidic or alkaline etching solution that is appropriately selected depending on the target to be etched. Examples of the acidic etching solution include an aqueous solution of an acidic component selected from hydrochloric acid, sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, oxalic acid, and phosphoric acid, and an aqueous solution of a mixture of an acidic component and a salt selected from ferric chloride, ammonium fluoride, and potassium permanganate. The acidic component may be a combination of a plurality of acidic components. Examples of the alkaline etching solution include an aqueous solution of an alkaline component selected from sodium hydroxide, potassium hydroxide, ammonia, organic amines, and salts of organic amines (e.g., tetramethylammonium hydroxide), and an aqueous solution of a mixture of an alkaline component and a salt (e.g., potassium permanganate). The alkaline component may be a combination of a plurality of alkaline components.

[0283] <Removal process> The method for producing a circuit wiring may include a step of removing the remaining pattern (a removing step). The removal step is not particularly limited and may be performed before or after each step, preferably after the etching step. The method for removing the remaining pattern is not particularly limited, but includes a method of removing the pattern by chemical treatment, and a method of removing the pattern by using a removing liquid is preferred. As a method for removing the pattern using a remover, a method in which the transferred object having the remaining pattern is immersed in the remover while stirring for 1 to 30 minutes can be mentioned. The temperature of the removal liquid is preferably 30 to 80°C, and more preferably 50 to 80°C.

[0284] Examples of the removal liquid include removal liquids in which an inorganic or organic alkaline component is dissolved in water, dimethyl sulfoxide, N-methylpyrrolidone, or a mixture thereof. Examples of the inorganic alkaline component include sodium hydroxide and potassium hydroxide. Examples of the organic alkaline component include primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium salt compounds. Alternatively, the removal may be performed by a known method such as a spray method, a shower method, or a paddle method using a removal liquid.

[0285] [Other steps] The method for producing a laminate and the method for producing a circuit wiring may include any steps (other steps) other than the steps described above. Examples of the exposure step, development step, and other steps that can be applied to the method for producing circuit wiring include the steps described in paragraphs

[0035] to

[0051] of JP-A-2006-023696.

[0286] <Step of reducing visible light reflectance> The method for producing a laminate and the method for producing a circuit wiring may include a step of performing a treatment for reducing the visible light reflectance of a part or all of a plurality of conductive layers of the transfer recipient. An example of a treatment for reducing the visible light reflectance is an oxidation treatment. When the transfer target has a conductive layer containing copper, the copper is oxidized to copper oxide, and the conductive layer is blackened, thereby reducing the visible light reflectance of the conductive layer. With regard to the treatment for reducing visible light reflectance, the following descriptions can be found by reference: paragraphs

[0017] to

[0025] of JP2014-150118A, and paragraphs

[0041] to

[0042] ,

[0048] , and

[0058] of JP2013-206315A, the contents of which are incorporated herein by reference.

[0287] <Step of forming an insulating film, step of forming a new conductive layer on the surface of the insulating film> The method for producing the circuit wiring preferably includes the steps of forming an insulating film on the surface of the circuit wiring, and forming a new conductive layer on the surface of the insulating film. Through the above steps, a first electrode pattern and an insulated second electrode pattern can be formed. The step of forming the insulating film is not particularly limited, and may be a known method for forming a permanent film. Alternatively, an insulating film having a desired pattern may be formed by photolithography using a photosensitive material having insulating properties. The step of forming a new conductive layer on the insulating film is not particularly limited, and for example, a new conductive layer having a desired pattern may be formed by photolithography using a photosensitive composition having conductivity.

[0288] In the method for producing the circuit wiring, a transferee including a plurality of conductive layers on both surfaces of the transferee is used, and circuits are formed sequentially or simultaneously on the conductive layers arranged on both surfaces of the transferee. With this configuration, a touch panel circuit wiring can be formed in which a first conductive pattern is formed on one surface of the transferee and a second conductive pattern is formed on the other surface of the transferee. It is also preferable to form the touch panel circuit wiring having such a configuration from both surfaces of the transferee by roll-to-roll.

[0289] [Application] The laminate and the circuit wiring produced by the laminate manufacturing method and the circuit wiring manufacturing method can be applied to various devices. Examples of devices equipped with the laminate or the circuit wiring produced by the above manufacturing method include a display device, a printed wiring board, a semiconductor package, and an input device, and a touch panel is preferable, and a capacitive touch panel is more preferable. The input device can be applied to a display device such as an organic EL display device and a liquid crystal display device.

[0290] [Method of Manufacturing Electronic Device] The transfer film may also be used in a method for manufacturing an electronic device. As the method for producing the electronic device, a method for producing an electronic device using the above-mentioned transfer film is preferable. In particular, the method for producing an electronic device preferably includes the method for producing the laminate described above. The electronic device may be, for example, an input device, preferably a touch panel, and may be applied to a display device such as an organic electroluminescence display device or a liquid crystal display device.

[0291] As a method for manufacturing a touch panel, for example, a method including a step of forming wiring for a touch panel by etching the conductive layer in an area where a resin pattern is not arranged in a laminate in which a transfer object (e.g., a substrate, a conductive layer (a conductive layer possessed by the substrate)) and a pattern manufactured using the above-mentioned transfer film are laminated in this order is also preferred, and a method using a pattern manufactured by a manufacturing method including the above-mentioned lamination step, the above-mentioned exposure step, and the above-mentioned development step is more preferred.

[0292] In the method for manufacturing a touch panel including a step of forming wiring for a touch panel, specific aspects of each step and the order in which each step is performed are as described above in <Method for manufacturing circuit wiring>, and preferred aspects are also the same. Furthermore, the method for manufacturing a touch panel including the step of forming wiring for a touch panel may include any step (other step) other than those described above. An example of a method for forming wiring for a touch panel is the method shown in FIG. 1 of WO 2016 / 190405.

[0293] The above-mentioned method for producing a touch panel produces a touch panel having at least a wiring for a touch panel. The touch panel preferably has a transparent substrate, an electrode, and an insulating layer or a protective layer. Examples of detection methods for touch panels include known methods such as a resistive film method, a capacitance method, an ultrasonic method, an electromagnetic induction method, and an optical method, with the capacitance method being preferred.

[0294] Examples of touch panels include in-cell types (e.g., those shown in Figures 5 to 8 of JP 2012-517051 A), on-cell types (e.g., those shown in Figure 19 of JP 2013-168125 A and those shown in Figures 1 and 5 of JP 2012-089102 A), OGS (One Glass Solution) types, TOL (Touch-on-Lens) types (e.g., those shown in Figure 2 of JP 2013-054727 A), various out-cell types (e.g., GG, G1 / G2, GFF, GF2, GF1, and G1F, etc.), and other configurations (e.g., those shown in Figure 6 of JP 2013-164871 A). An example of the touch panel is described in paragraph

[0229] of JP2017-120345A.

[0295] In the method for producing an electronic device using a transfer film, it is also preferred that the produced electronic device contains a resin pattern as a cured film (particularly when the transfer film contains a negative photosensitive composition layer). Such a cured film of the resin pattern can be used as a protective film (permanent film) that covers a part or all of the electrodes of an electronic device (such as a touch panel). By disposing the cured film of the resin pattern as a protective film (permanent film) on an electrode, it is possible to prevent defects such as metal corrosion, an increase in electrical resistance between the electrode and the driving circuit, and disconnection. Other uses of the cured film of the resin pattern include, for example, various electrode protective films, planarizing films, overcoat films, hard coat films, passivation films, partitions, spacers, microlenses, optical filters, and antireflection films. EXAMPLES

[0296] The present invention will be specifically described below with reference to examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of this specification. Therefore, the scope of the present invention is not limited to the specific examples shown below. In addition, unless otherwise specified, "parts" and "%" are based on mass. In the following examples, the weight average molecular weight (Mw) is the weight average molecular weight determined by gel permeation chromatography (GPC) in terms of polystyrene.

[0297] [Temporary Support] <Synthesis of polyester 1> As shown below, polyester 1 (hereinafter also referred to as "PET1") (Sb catalyst-based PET), which is the raw material for the temporary support, was synthesized in a continuous polymerization apparatus using the direct esterification method in which terephthalic acid and ethylene glycol are directly reacted to distill off water, esterified, and then polycondensed under reduced pressure.

[0298] (Esterification reaction) High-purity terephthalic acid (4.7 tons) and ethylene glycol (1.8 tons) were mixed in the first esterification reaction tank over 90 minutes to form a slurry, which was continuously fed to the first esterification reaction tank at a flow rate of 3800 kg / h. Furthermore, an ethylene glycol solution of antimony trioxide was continuously fed and reacted at a reaction tank temperature of 250°C with stirring for an average residence time of about 4.3 hours. At this time, antimony trioxide was continuously added so that the amount of Sb added was 150 ppm in elemental terms.

[0299] This reaction product was transferred to a second esterification reaction tank and reacted with stirring for an average residence time of 1.2 hours at a reaction tank temperature of 250° C. An ethylene glycol solution of magnesium acetate and an ethylene glycol solution of trimethyl phosphate were continuously supplied to the second esterification reaction tank so that the Mg (magnesium) addition amount was 65 ppm by mass and the P (phosphorus) addition amount was 35 ppm by mass, in elemental equivalent values.

[0300] (Polycondensation reaction) The esterification reaction product obtained above was continuously fed to a first polycondensation reactor, and the mixture was stirred at a reaction temperature of 270° C. and a pressure inside the reactor of 20 torr (2.67×10 -3 The polycondensation was carried out at a pressure of 1.8 MPa for an average residence time of about 1.8 hours.

[0301] The mixture was then transferred to a second condensation reactor, where it was stirred at a temperature of 276° C. and a pressure of 5 torr (6.67×10 -4 The reaction (polycondensation) was carried out under conditions of a pressure of 1.2 MPa and a residence time of about 1.2 hours.

[0302] The mixture was then transferred to a third polycondensation reactor, where the temperature inside the reactor was 278° C. and the pressure inside the reactor was 1.5 torr (2.0×10 -4 The mixture was reacted (polycondensed) under conditions of a pressure of 1.5 MPa and a residence time of 1.5 hours to obtain reaction product 1 (polyethylene terephthalate (PET)).

[0303] Next, the obtained reaction product 1 was discharged into cold water in the form of a strand and immediately cut into polyester pellets <cross section: major axis about 4 mm, minor axis about 2 mm, length: about 3 mm> to obtain PET 1. The IV (intrinsic viscosity) of the obtained PET 1 was 0.63.

[0304] <Synthesis of polyester 2> The dried UV absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (10 parts by mass) and PET1 (90 parts by mass) were mixed and pelletized using a kneading extruder in the same manner as in the preparation of PET1 described above, to obtain polyester 2 containing a UV absorber, which is a raw material for the temporary support (hereinafter also referred to as "PET2").

[0305] <Production of temporary support> (Temporary Support C-1) PET1 (90 parts by mass) and PET2 (10 parts by mass) were dried to a moisture content of 20 ppm by mass or less, then fed into hopper 1 of a single-screw kneading extruder 1 with a diameter of 50 mm, and melted at 300°C in extruder 1 (intermediate layer II). Also, PET1 was dried to a moisture content of 20 ppm by mass or less, then charged into a hopper 2 of a single-screw kneading extruder 2 with a diameter of 30 mm, and melted at 300° C. in the extruder 2 (outer layer I, outer layer III). These two kinds of polymer melts were passed through a gear pump and a filter set having one filter (8 μm mesh, i.e., 8 μm hole size), and then laminated in a two-kind, three-layer merging block so that the polymer extruded from extruder 1 was the middle layer (II layer) and the polymer extruded from extruder 2 was the outer layers (I and III layers), and extruded into a sheet from a die with a width of 120 mm. The extrusion conditions for the molten resin were a pressure fluctuation of 1% and a temperature distribution of the molten resin of 2%, and the molten resin was extruded from the die. Specifically, the back pressure was increased by 1% relative to the average pressure in the barrel of the extruder, and the piping temperature of the extruder was heated to a temperature 2% higher than the average temperature in the barrel of the extruder. The molten resin extruded from the die was extruded onto a cooling cast drum set at a temperature of 25°C, and was adhered to the cooling cast drum using an electrostatic application method. The resin temperature during extrusion was 300°C. The resin temperature when adhered to the cooling drum was 277°C. The resin was peeled off using a peeling roll arranged opposite the cooling cast drum, to obtain an unstretched polyester film 1. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of the I layer, II layer, and III layer was 10 (I layer):80 (II layer):10 (III layer).

[0306] Using a stretching roll with a surface roughness Ra of 0.2 μm, the unstretched polyester film 1 obtained was stretched 4.2 times in the longitudinal direction at 110 ° C. Furthermore, it was subsequently stretched 4.5 times in the transverse direction under hot air at 115 ° C. using a stenter, and then heat-treated at 215 ° C. for 4 seconds under constant tension, and then subjected to relaxation treatment of 0.1% in the longitudinal direction and 3.2% in the transverse direction to obtain a biaxially stretched polyester film 1' with a thickness of 16 μm. The obtained biaxially stretched polyester film 1' was slit with a slitter to obtain a temporary support C-1.

[0307] (Temporary support C-2) The thickness of the unstretched polyester film 1 obtained in the above-mentioned <Production of temporary support> was adjusted to 16 μm, and the film was stretched 4.0 times in the longitudinal direction and 4.7 times in the transverse direction, but the film was produced in the same manner as for temporary support C-1 to obtain a biaxially stretched polyester film 2' having a thickness of 16 μm. The obtained biaxially stretched polyester film 2' was slit with a slitter to obtain temporary support C-2.

[0308] (Temporary support C-3) The thickness of the unstretched polyester film 1 obtained in the above-mentioned <Production of temporary support> was adjusted to 25 μm, and the film was stretched 3.8 times in the longitudinal direction and 4.8 times in the transverse direction, but the film was produced in the same manner as in the case of temporary support C-1 to obtain a biaxially stretched polyester film 3' having a thickness of 25 μm. The obtained biaxially stretched polyester film 3' was slit with a slitter to obtain temporary support C-3.

[0309] (Temporary support C-4) A biaxially stretched polyester film 4' having a thickness of 16 μm was obtained in the same manner as in Temporary Support C-1, except that the thickness of the unstretched polyester film 1 obtained in the above-mentioned <Production of Temporary Support> was adjusted, stretched 4.1 times in the longitudinal direction, and stretched 4.8 times in the transverse direction under hot air at 123° C., to obtain a biaxially stretched polyester film 4' having a thickness of 16 μm. The obtained biaxially stretched polyester film 4' was slit with a slitter to obtain Temporary Support C-4.

[0310] (Temporary support C-5) The thickness of the unstretched polyester film 1 obtained in the above-mentioned <Production of temporary support> was adjusted to 25 μm, and the film was stretched 3.8 times in the longitudinal direction and 4.8 times in the transverse direction under hot air at 110° C., and the relaxation treatment in the transverse direction was set to 2.4%, but the film was produced in the same manner as temporary support C-1 to obtain a biaxially stretched polyester film 5′ having a thickness of 25 μm. The obtained biaxially stretched polyester film 5′ was slit with a slitter to obtain temporary support C-5.

[0311] [Binder Polymer] <Synthesis of binder polymer P-1> Propylene glycol monomethyl ether (82.4 g, FUJIFILM Wako Pure Chemical Corporation) was charged into a flask to prepare a solution. The obtained solution was heated to 90°C under a nitrogen gas flow. A solution of styrene (38.4 g, FUJIFILM Wako Pure Chemical Corporation), dicyclopentanyl methacrylate (30.1 g, Fancryl FA-513M, Hitachi Chemical Co., Ltd.), and methacrylic acid (34.0 g, FUJIFILM Wako Pure Chemical Corporation) dissolved in propylene glycol monomethyl ether (20 g), and a solution of polymerization initiator V-601 (5.4 g, FUJIFILM Wako Pure Chemical Corporation) dissolved in propylene glycol monomethyl ether acetate (43.6 g, FUJIFILM Wako Pure Chemical Corporation) were simultaneously added dropwise to the heated solution over a period of 3 hours. After the dropwise addition was completed, V-601 (0.75 g) was added to the solution three times at 1-hour intervals. The solution was then reacted for another 3 hours. The obtained solution was then diluted with propylene glycol monomethyl ether acetate (58.4 g) and propylene glycol monomethyl ether (11.7 g). The diluted solution was heated to 100° C. under an air flow, and tetraethylammonium bromide (0.53 g, FUJIFILM Wako Pure Chemical Industries, Ltd.) and p-methoxyphenol (0.26 g, FUJIFILM Wako Pure Chemical Industries, Ltd.) were added to the solution. Glycidyl methacrylate (25.5 g, NOF Corporation, Blenmer GH) was added dropwise to the obtained solution over 20 minutes. The obtained solution was reacted at 100° C. for 7 hours to obtain a solution of binder polymer P-1. The solid content concentration of the obtained solution was 36.5% by mass. The obtained binder polymer had each of the structural units shown in Table 1, and had a weight average molecular weight (Mw) of 17000 in terms of standard polystyrene measured by GPC, a polydispersity of 2.4, and an acid value of 94.5 mgKOH / g. The amount of residual monomer measured by gas chromatography was less than 0.1% by mass relative to the solid content of the binder polymer for each monomer. The solid content refers to the components excluding the solvent. Even if the above components are in a liquid state, they are included in the solid content.

[0312] In Table 1, the structural units other than the structural unit having a (meth)acryloyl group are shown by the abbreviation of the monomer that forms each structural unit. A structural unit having a (meth)acryloyl group is shown in the form of an addition structure between monomers. For example, MAA-GMA means a structural unit in which glycidyl methacrylate is added to a structural unit derived from methacrylic acid. St: styrene MAA-GMA: A structural unit in which glycidyl methacrylate is added to a structural unit derived from methacrylic acid. MAA: Methacrylic acid MMA: Methyl methacrylate EA: Ethyl acrylate BzMA: benzyl methacrylate DCPMA: dicyclopentanyl methacrylate

[0313] [Table 1]

[0314] <Synthesis of binder polymers P-2 to P-4> The synthesis was carried out in the same manner as P-1, except that the type and amount of the monomer and the amount of the initiator were changed. The solid content concentration of the obtained solution was 36.3% by mass. The obtained binder polymer had each of the structural units shown in Table 1. The amount of residual monomer measured by gas chromatography was less than 0.1% by mass relative to the solid content of the binder polymer for each monomer.

[0315] <Synthesis of binder polymer P'-1> Propylene glycol monomethyl ether (270.0 g) was added to a three-neck flask, and the temperature was raised to 70° C. under a nitrogen stream while stirring. Meanwhile, allyl methacrylate (45.6 g, FUJIFILM Wako Pure Chemical Industries, Ltd.) and methacrylic acid (14.4 g) were dissolved in propylene glycol monomethyl ether (270.0 g), and V-65 (3.94 g, FUJIFILM Wako Pure Chemical Industries, Ltd.) was further dissolved to prepare a dropping solution, and the resulting dropping solution was dropped into a three-neck flask over 2.5 hours. The resulting solution was reacted for 2 hours while stirring. Thereafter, the temperature of the resulting solution was allowed to cool to room temperature, and the resulting solution was dropped into ion-exchanged water (2.7 L) while stirring the ion-exchanged water, and reprecipitation was performed to obtain a suspension. The suspension was filtered by putting it into a Nutsche with filter paper, and the filtrate was further washed with ion-exchanged water to obtain a wet binder polymer P'-1 powder. Next, the mixture was dried by blowing air at 45°C, and it was confirmed that the mixture had reached a constant weight, and binder polymer P'-1 was obtained as a powder with a yield of 70%. The structural formula of binder polymer P'-1 is shown below. The ratio of each structural unit contained in the binder polymer below is expressed as mass%.

[0316] [ka]

[0317] [Blocked isocyanate compound Q-1] Butanone oxime (453 g, Idemitsu Kosan Co., Ltd.) was dissolved in methyl ethyl ketone (700 g) under a nitrogen stream to obtain a solution. 1,3-bis(isocyanatomethyl)cyclohexane (500 g, cis-trans isomer mixture, Mitsui Chemicals Co., Ltd., Takenate 600) was added dropwise to the obtained solution over 1 hour under ice cooling, and the solution was further reacted for 1 hour after the dropwise addition. The obtained solution was then heated to 40°C and further reacted for 1 hour. 1 Completion of the reaction was confirmed by 1 H-NMR (nuclear magnetic resonance) and HPLC (high performance liquid chromatography), and a methyl ethyl ketone solution of a blocked isocyanate compound Q-1 represented by the following structural formula was obtained.

[0318] [ka]

[0319] [Preparation of Photosensitive Composition] In each Example or Comparative Example, materials A-1 to A-5 were prepared as photosensitive compositions having the compositions shown in Table 2 below. In Table 2, the numerical value of each component indicates the content (parts by mass) of each component, and the amount of binder polymer means the amount of binder polymer solution (solid concentration 36.3% by mass).

[0320] [Table 2]

[0321] [Preparation of Refractive Index Adjusting Layer Forming Composition] Next, a material B-1, which is a composition for forming a refractive index adjusting layer, was prepared according to the composition shown in Table 3 below.

[0322] [Table 3]

[0323] Example 1 On the temporary support C-1 prepared above, a slit nozzle was used to apply a coating amount of the photosensitive composition A-1 so that the thickness after drying would be 5.5 μm, and the solvent was evaporated in a drying zone at 100 ° C. to form a photosensitive composition layer 1. Furthermore, a slit nozzle was used to apply a coating amount of the refractive index adjustment layer forming composition B-1 so that the thickness after drying would be 70 nm, and the composition was dried at a drying temperature of 80 ° C. to form a refractive index adjustment layer 1. A polypropylene film (Trefan 25A-KW37, manufactured by Toray Industries, Inc.) having a thickness of 25 μm was pressed onto the refractive index adjustment layer as a protective film to prepare a transfer film 1 of Example 1.

[0324] [Examples 2 to 4 and Comparative Examples 1 to 3] Transfer films 2 to 4 and 1' to 3' of Examples 2 to 4 and Comparative Examples 1 to 3 were produced in the same manner as in Example 1, except that the components, materials, thicknesses, etc. were changed according to Table 4.

[0325] [Examples 5 to 8] Transfer films 5 to 8 were prepared in the same manner as in Example 1, except that when forming the photosensitive composition layer, the components, materials, and thicknesses, etc. were changed according to Tables 2 and 4, and no refractive index adjustment layer was formed.

[0326] <Production of Laminate> The method for producing the laminate will be described with reference to FIG. A substrate (substrate 43 having a step) was prepared on a substrate (a COP film having an ITO transparent electrode pattern with a film thickness of 50 μm) having a copper conductive portion with a rectangular shape of 2 cm in length and 5 cm in width when viewed from above the substrate, with the step thickness constituting the step being 100 nm and the lamination direction 42 being the vertical direction. The protective film of each of the transfer films of the Examples and Comparative Examples was peeled off, and the exposed surface of the photosensitive composition side (refractive index adjusting layer) was continuously laminated in the lamination direction 42 shown in Figure 1 so as to cover all of the steps of the resulting substrate having steps, under conditions of a rubber roller temperature of 100°C, a linear pressure of 100 N / cm, and a conveying speed of 4.0 m / min, to obtain a laminate with a photosensitive composition layer laminated thereon. This lamination method includes a step-up process in which a photosensitive composition layer is laminated in this order from the lower part of a step constituting a step to the upper part of the step, and a step-down process in which a photosensitive composition layer is laminated in this order from the upper part of a step constituting a step to the lower part of the step, once each.

[0327] 〔evaluation〕 <Measurement of storage modulus> The longitudinal and lateral directions of each of the temporary supports C-1 to C-5 prepared above were cut into a size of 5 mm x 30 mm. The cut samples were conditioned at 25°C and 60% RH (relative humidity) for 2 hours or more, and then measured with a dynamic viscoelasticity measuring device (Vibron: DVA-225 (manufactured by IT Measurement and Control Co., Ltd.)) at a grip distance of 20 mm, a heating rate of 2°C / min, a measurement temperature range of 30°C to 150°C, and a frequency of 1 Hz in the longitudinal direction of the sample, to measure the storage modulus (E a1 , E a2 , E b1 and E b2 ) was sought.

[0328] <Evaluation of wrinkles during lamination> The wrinkles and fine wrinkles occurring in at least one of the refractive index adjusting layer, the photosensitive composition layer, and the temporary support of the laminate obtained in the above-mentioned <Prepared Laminate> were evaluated according to the following criteria. In the following evaluation criteria, it is preferably A or B. Note that wrinkles refer to wrinkles of a size that can be observed with the naked eye, and fine wrinkles refer to wrinkles of a size that cannot be observed with the naked eye but can be observed with an optical microscope at a magnification of 20 times. (Evaluation Criteria) A: No wrinkles are found in the laminate when visually observed over a continuous length of 200 m. 2 When the laminate in the range is observed under an optical microscope at a magnification of 20 times, no fine wrinkles are found. B: No wrinkles are found in the laminate when visually observed over a continuous length of 200 m. 2 When the laminate in the range was observed under an optical microscope at a magnification of 20 times, the number of fine wrinkles was 1 to 10. C: No wrinkles are found in the laminate when visually observed over a continuous length of 200 m. 2 When the laminate in the range was observed under an optical microscope at 20 times magnification, 11 or more fine wrinkles were found. D: Wrinkles were confirmed in the laminate when visually observed over a continuous 200 m length of the laminate.

[0329] The evaluation results are shown in Table 4. The descriptions in the table indicate the following. "E a1 The " column shows the storage modulus E at 100 ° C in the short direction of the temporary support a1 Shows. "E a2 The " column shows the storage modulus E at 100 ° C in the longitudinal direction of the temporary support. a2 Shows. "E b1 The " column shows the storage modulus E at 80 ° C in the short direction of the temporary support b1 Shows. "E b2 The " column shows the storage modulus E at 80 ° C in the longitudinal direction of the temporary support b2 Shows. "E a1 / E a2 The " column shows the storage modulus E at 100 ° C in the longitudinal direction of the temporary support. a2 Storage modulus E at 100 ° C in the short direction of the temporary support a1 The ratio of is shown. "E b1 / E b2 The " column shows the storage modulus E at 80 ° C in the longitudinal direction of the temporary support b2 Storage modulus E at 80 ° C in the short direction of the temporary support b1 The ratio of is shown. The "X" column indicates the value calculated by the following formula (1). X={〔(E b1 / E b2 )-(E a1 / E a2 )〕 / (E b1 / E b2 )}×100 Equation (1) The "geometric mean of 100°C" column is E a1 and E a2 The square root of the product of (100°C) = √(E a1 ×E a2 )) is shown.

[0330] [Table 4]

[0331] As shown in Table 4 above, it was confirmed that the desired effects were obtained when the transfer film of the present invention was used. From the comparison of Examples 1 to 4, the storage modulus E at 100 ° C. in the longitudinal direction of the temporary support a2 Storage modulus E at 100 ° C in the short direction of the temporary support a1 The ratio (E a1 / E a2 It was confirmed that the effect was better when E a1 / E a2 It was confirmed that the effect was even better when the ratio was 1.25 or less. Furthermore, by comparing Examples 1 and 4 with Examples 2 to 3, it was confirmed that a more excellent effect was achieved when X calculated by the above formula (1) was 7.00% or less.

[0332] Example 9 The resolution and peelability of the wiring pattern obtained when the transfer films of Examples 1 to 8 were used as etching resists for forming wiring were evaluated by the following method. A copper layer with a thickness of 200 nm was formed on a polyethylene terephthalate (PET) film with a thickness of 100 μm by sputtering, thereby producing a PET substrate with a copper layer.

[0333] <Resolution> The transfer film of any one of Examples 1 to 8 in the form of a roll prepared was unwound, and the protective film was peeled off from the transfer film. Next, the transfer film and the copper layer-attached PET substrate were attached to each other so that the surface (refractive index adjustment layer) of the transfer film opposite to the temporary support side exposed by the peeling off of the protective film and the copper layer of the copper layer-attached PET substrate were in contact with each other to obtain a laminate. This attachment process was carried out under the conditions of a roll temperature of 100°C, a linear pressure of 1.0 MPa, and a linear speed of 4.0 m / min. The photosensitive composition layer was exposed to light from the temporary support side of the obtained laminate through a photomask with an ultra-high pressure mercury lamp (main exposure wavelength: 365 nm). The photomask used for exposure had a line and space pattern with a width ratio (duty ratio) of 1:1 and a line width and space width of 50 μm. The exposure dose for the photosensitive composition layer was adjusted so that the line width of the resin pattern formed by exposure with the irradiation light passing through the area where the line width and space width of the line and space pattern are 50 μm was 50 μm. Thereafter, the temporary support was peeled off from the exposed laminate, and shower development was performed for 30 seconds using a 1.0 mass % sodium carbonate aqueous solution at a liquid temperature of 25 ° C. By this development process, the unexposed photosensitive composition layer was removed from the laminate, and a resin pattern having a line and space pattern on the surface of the copper layer was produced. In any case where the transfer film of Examples 1 to 8 was used, a resin pattern with good resolution was obtained.

[0334] <Removability> The laminates having a resin pattern on the surface of the copper layer obtained in the above <Resolution> were etched using a copper etching solution (Cu-02, manufactured by Kanto Chemical Co., Ltd.) to etch the copper layer in the area where the resin pattern was not arranged. The laminates subjected to the copper etching treatment were each immersed in a stripping solution (KP-301, manufactured by Kanto Chemical Co., Ltd.) at 40°C, and the stripping solution was stirred at 100 rpm. In all of the laminates having resin patterns formed using any of the transfer films of Examples 1 to 8, the resin patterns were completely peeled off from the surface of the copper layer within 2 minutes after the laminate was immersed in the stripping solution, showing good peelability. The obtained laminates were further washed with water and dried to obtain copper wiring boards on which copper was drawn in a line and space pattern. In all of the cases where any of the transfer films of Examples 1 to 8 was used, a well-resolved copper wiring pattern could be obtained. [Explanation of symbols]

[0335] 1A Board 41 Steps that make up a step Top of step 41a Side of tier 41b Bottom of tier 41c 42 Lamination Direction 43 Substrate with steps 44 Area along the step

Claims

1. A long-sized transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support, Storage modulus E at 100° C. in the longitudinal direction of the temporary support a2 Storage modulus E at 100 ° C. in the short direction of the temporary support a1 is 1.40 or less, The storage elastic modulus E a1 is 1.00 to 5.00 GPa, The storage elastic modulus E a2 is 1.00 to 5.00 GPa, The transfer film, wherein the photosensitive composition layer has a thickness of 3.0 to 20.0 μm.

2. A long-sized transfer film having a temporary support and a photosensitive composition layer disposed on the temporary support, Storage modulus E at 100° C. in the longitudinal direction of the temporary support a2 Storage modulus E at 100 ° C. in the short direction of the temporary support a1 is 1.40 or less, The storage elastic modulus E a1 is 1.00 to 5.00 GPa, The storage elastic modulus E a2 is 1.00 to 5.00 GPa, The transfer film, wherein the photosensitive composition layer has a thickness of 3.0 to 20.0 μm. However, this does not include the case where the photosensitive composition layer is a photosensitive composition layer formed using a photosensitive resin composition containing (A) a binder polymer having a structural unit derived from styrene, (B) a photopolymerizable compound, (C) a photopolymerization initiator, and (D) a polyglycerin alkyl ester type surfactant.

3. The transfer film according to claim 1 or 2, wherein X calculated by formula (1) is 7.00% or less. X = {[((E b1 / E b2 ) - (E a1 / E a2 )) / (E b1 / E b2 ))} × 100 Equation (1) E a1 : Storage modulus (GPa) at 100 ° C. in the short direction of the temporary support E a2 : Storage modulus (GPa) at 100 ° C. in the longitudinal direction of the temporary support E b1 : Storage modulus (GPa) at 80 ° C. in the short direction of the temporary support E b2 : Storage modulus (GPa) at 80 ° C. in the longitudinal direction of the temporary support

4. The storage modulus E of the temporary support in the short direction at 100 ° C. a1 and the storage modulus E in the longitudinal direction of the temporary support at 100 ° C. a2 The transfer film according to any one of claims 1 to 3, wherein a geometric mean of the modulus of elasticity and the modulus of elasticity is 1.00 GPa or more.

5. The transfer film according to any one of claims 1 to 4, wherein the temporary support has a thickness of 40.0 µm or less.

6. The transfer film according to any one of claims 1 to 5, wherein the photosensitive composition layer contains a binder polymer, a polymerizable compound, and a polymerization initiator.

7. The transfer film according to any one of claims 1 to 6, further comprising a refractive index adjusting layer disposed on the photosensitive composition layer.

8. The transfer film according to any one of claims 1 to 7, wherein the photosensitive composition layer is used for forming an electrode protective film for a touch panel.

9. The transfer film according to any one of claims 1 to 8, wherein the temporary support has an intermediate layer and outer layers laminated on both sides thereof.

10. The transfer film according to any one of claims 1 to 9, wherein the photosensitive composition layer is formed on the temporary support.

11. The transfer film according to any one of claims 1 to 10, wherein the temporary support has a thickness of 30.0 µm or less.

12. a lamination step of laminating a surface of the transfer film according to any one of claims 1 to 11 opposite to the temporary support to a transferee to obtain a transferee with a photosensitive composition layer having the transferee, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; A developing step of developing the exposed photosensitive composition layer to form a pattern, The method for producing a laminate further comprises a peeling step of peeling the temporary support from the photosensitive composition layer-attached object between the laminating step and the exposing step, or between the exposing step and the developing step.

13. a lamination step of laminating a surface of the transfer film according to any one of claims 1 to 11 opposite to the temporary support to a transfer-receiving body including a conductive layer to obtain a transfer-receiving body with a photosensitive composition layer having the transfer-receiving body, the photosensitive composition layer, and the temporary support in this order; an exposure step of pattern-exposing the photosensitive composition layer; a developing step of developing the exposed photosensitive composition layer to form a pattern; an etching step of etching the conductive layer in areas where the pattern is not disposed; The method for producing circuit wiring further comprises a peeling step of peeling the temporary support from the transfer target body with the photosensitive composition layer between the laminating step and the exposure step, or between the exposure step and the development step.

14. The method for producing a laminate according to claim 12 , wherein the transferred object is a substrate having a step.

Citation Information

Patent Citations

  • Photosensitive resin for producing color filter

    JP1994324210A

  • Biaxially oriented polyester film for dry film resist supporter

    JP2016087854A

  • Photosensitive resin composition, photosensitive element, method for forming resist pattern and method for manufacturing printed wiring board

    JP2019008001A

  • Process for producing layered product, layered product, substrate for liquid-crystal display, liquid-crystal display element, and liquid-crystal display

    WO2007091537A1